Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Iron-doped porous carbon derived from Fe-MOFs for activation of peroxymonosulfate to degrade organic pollutions - Wen Huang; Xin Chen; Yuhang Fu; Lei Chen; Ruizhen Li; Qijun Cao; Hongchen Ma; Jiangqiang Zhang; Chun wang (Journal of Environmental Chemical Engineering, 2026)

High-surface-area g-C3N4/ZIF-8 heterojunction for synergistic radical and non-radical photocatalytic peroxymonosulfate activation toward antibiotic degradation: Mechanistic insight and membrane application - Ying-Ying Zhang; Si-Han Guo; Wu-He Ji Pi; Qing-Tong Dong; Qi Huang; Jing Bu; Li-Xuan Kou; Chun Li; Quan-Liang Chen (Journal of Environmental Chemical Engineering, 2026)

Gradient sulfur-vacancy engineering of MoS2 for selective non-radical peroxymonosulfate activation: Toward enhanced interference resistance in complex water matrix - Xuexia Guo; Ting Li; Huinan Zhao; Wenbin Huang; Lu Zeng; Zhangnan Yao; Shuanghong Tian; Chun He (Journal of Environmental Chemical Engineering, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Structural characterization and systemic hypoglycemic effects of a new high-molecular-weight α-glucan from Grifola frondosa - Wei Zhong; Juan Wang; Yu Ding; Longhua Huang; Huixiang Tian; Qinzhao Ruan; Xiangmin Li; Yuanchao Liu; Tianqiao Yong; Shaodan Chen; Nan Miao; Huiyang Guo; et al. (Carbohydrate Polymers, 2026)

Chemotaxonomic significance of dipeptides and flavonoids in the whole plants of Euphorbia dentata Michx - Ye Chang; Tian-Yi Chun; Xue Wen; Xiang-Ting He; Guo-Wei Zhang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2026)

Flooding and salinity increase from sea-level rise alters microbial community structure and reduces CO2 emissions in a subtropical estuarine wetland - Li Hou; Zhuang Huang; Chun Wang; Xiaoying Ren; Chuan Tong; Weiqi Wang (Applied Soil Ecology, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Stability regulation and co-pigmentation effects of black wolfberry anthocyanin-loaded core–shell nanocapsules under simulated food matrix conditions - Jiajun Huang; Yangnan Yan; Chun Li; Libin Ma; Zhehao Li; Xuan Wang; Shuwen Liu; Xianghong Xie (Food Bioscience, 2026)

Structure-based machine learning model for discovering pregnane X receptor (PXR) agonists and biological activity validation - Fang-Fang Huang; Ying Luo; Hao Chen; Yu-Huan Meng; Wei Li; Hong Liang; Chun-Zhi Ai (Archives of Toxicology, 2026)

A Critical Review of Platform Motion Effects on the Aerodynamic Performance, Wake Dynamics and Load Responses of Floating Vertical Axis Wind Turbines - Haoda Huang; Qingsong Liu; Chun Li; Wanfu Zhang; Musa Bashir; Gregorio Iglesias (Journal of Marine Science and Engineering, 2026)
Floating vertical-axis wind turbines (VAWTs) couple intrinsically unsteady rotor aerodynamics with the motions of their supporting platforms, producing complex temporal variations in power output, aerodynamic loads, and wake transport. A structured search of the Web of Science Core Collection and Scopus, supplemented by citation tracking, identified peer-reviewed studies published from database inception to 30 June 2026. The reviewed computational fluid dynamics (CFD) studies were classified as decoupled or fully coupled according to whether bidirectional feedback between the flow field and platform response was resolved. The evidence shows that motion-induced velocities alter blade-relative inflow and effective angle of attack, thereby modifying dynamic stall, loads, and wake evolution. Scaled testing is limited by the incompatibility between Froude and Reynolds similitude. Under identical pitch conditions, the mean power coefficient increased by 16.42% at full scale but decreased by 56.71% at 1:100 scale. Platform motion generally increases power and load fluctuations but may accelerate wake recovery; effects on mean performance remain configuration- and scale-dependent, so no universally optimal rotor-platform design has emerged. Overall, this review provides an integrated understanding of the effects of platform motion on the unsteady aerodynamics, load responses, and wake evolution of floating VAWTs, and clarifies the applicability of decoupled and fully coupled CFD methods to mechanism identification and system-level assessment.

Crashworthiness and Impact Resilience of Offshore Wind Turbines Protected by Honeycomb Sandwich Fenders - Kunpeng Liu; Haoda Huang; Wanyong Zhang; Wanfu Zhang; Chun Li (Journal of Marine Science and Engineering, 2026)
Owing to transportation, installation, grid-connection, and maintenance requirements, nearshore offshore wind farms are often located close to busy shipping routes, substantially increasing the risk of ship–offshore wind turbine (OWT) collisions. To enhance the impact resilience of OWT support structures against ship collisions, a novel honeycomb sandwich fender is proposed for tower protection. Nonlinear transient analyses were performed using ANSYS/LS-DYNA to simulate a 5000 t ship traveling at 2 m/s and colliding with a 4 MW OWT supported by a single-column tripod foundation. The effects of rubber and aluminum foam cores on the crashworthiness and protective performance of the fender were compared. The results show that the rubber core stores collision energy through recoverable large deformation and releases most of the stored energy during unloading, resulting in pronounced energy restitution and prolonged structural excitation. By contrast, the aluminum foam core dissipates 7.5 MJ through cell-wall buckling, progressive crushing, and plastic collapse, corresponding to 75% of the initial kinetic energy of the ship. Compared with the rubber-core fender, the higher initial stiffness of the aluminum foam increases the peak contact force by 23.1%, from 13.0 to 16.0 MN. However, its irreversible energy-dissipation mechanism reduces the maximum tower-top displacement by 40.0%, from 1.25 to 0.75 m, and decreases the residual tower stress after three successive collisions by 25.0%, from 200 to 150 MPa. These results demonstrate that, despite transmitting a higher peak contact force, the aluminum foam fender provides more effective overall protection under the collision conditions considered because of its greater irreversible energy-dissipation capacity.

Correction: New 1,2,3-triazole-linked (±)-agrimonolide derivatives as anti-ulcerative colitis agents inhibiting JAK1/STAT3 pathways - Xiao Zhang; Ming-Qian Ju; Heng-Li Yang; Chun-Fei Zhang; Mao-Kui Huang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2026)

Experimental investigation of seismic response of waste dump slopes under pre- and post‑rainfall conditions - Tao Jiang; Shenghua Cui; Jian Lv; Wei Huang; Mengjie Yang; Gong Chenhua; Yufei Liang; Chun Zhu; Xiaoshuang Li (Transportation Geotechnics, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Investigation of the coupled dynamics and response correlations of a 10-MW Triple-spar floating offshore wind turbine under variable wind-wave-current conditions - Dinghong Lu; Zifei Xu; Haoda Huang; Qingsong Liu; Yangtian Yan; Weipao Miao; Chun Li; Minnan Yue (Ocean Engineering, 2026)

Bio-inspired semi-submersible platform for improving the hydrodynamic stability of floating vertical-axis wind turbines - Kunpeng Liu; Haoda Huang; Qingsong Liu; Qiang Zhang; Chun Li; Gregorio Iglesias; Jin Wang; Musa Bashir (Ocean Engineering, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Thermally buffered remnant melts sustain explosivity after caldera collapse: Cryptotephra evidence from Aira, Japan - Xuan-Yu Chen; Yi-Gang Xu; Xiao-Long Huang; Ji-Hoon Kim; Shuang Yan; Peng-Li He; Myong-Ho Park; Jong-Hwa Chun (Earth and Planetary Science Letters, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Exploration and identification of antifungal antibiotics from Streptomyces TRM 68022 based on OSMAC strategy - Yi-Huang Chen; Chun-Yang Zhang; Feng Zhang; Fei Yin; Yu-Xin Si; Ying-Ying Xia; Jia-Xin Zhang; Yi-Fei Li; Xiao-Xia Luo (Biocatalysis and Agricultural Biotechnology, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

A universal geometric model of egg shape with sine-based deformation - Ching-Wei Cheng; Chia-Chun Lai; Ping-Kun Tsai; Ko-Jung Huang; Cheng-Han Li (Biosystems Engineering, 2026)

Targeted sequestration of antimony via adsorption-induced topological transformation on supramolecular microcrystal-functionalized biochar - Xianke Wan; Zhixuan Yang; Bowei Chen; Ziyi Yu; Jun Nie; Zhiguo Wang; Chun Zhang; Jiajia Wang; Chunhui Li; Wei Huang (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Straw return coupled with subsoiling tillage reduces N₂O emissions and increases nitrogen content under long-term (12 years) trial in a coastal saline cotton field - Han Wang; Zhitao Liu; Qiyuan Guo; Lunxiao Shang; Longhao Zhou; Jiaxue Zhao; Ting Huang; Xiaoyu Li; Chenxi Shi; Baltaevich Ahmedov Miraziz; Xianliang Song; Xiaopei Zhang; et al. (Agriculture, Ecosystems & Environment, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

A robotic harvesting system for occluded cucumbers using F2SA-YOLOv8 and HVSC - Zhi-Hong Huang; Chun-Ta Chen; Naoki Ikegaya; Tien‑Li Chang; Kun‑Cheng Ke; Yi-Chia Chen (Computers and Electronics in Agriculture, 2026)

A distinct zearalenone detoxification strategy mediated by cytochrome P450 - Ziwei Liu; Rouming Peng; Qian Li; Chun-Chi Chen; Lilan Xin; Kangkang Li; Jian-Wen Huang; Xin Liu; Xiaodong Zhang; Linzhen Hu; Shangwen Luo; Haibing Zhou; et al. (Food Chemistry, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Manipulating non-radical pathway preference in PMS-mediated phenolic degradation: Substituent-dependent catalyst-pollutant interfacial interaction over single-atom Fe-N-C - Fan Huang; Xianhu Long; Ting Li; Xuexia Guo; Lingling Hu; Huinan Zhao; Shuanghong Tian; Minhua Su; Chun He (Chemical Engineering Journal, 2026)

Effects of functional spaces on small logistics facilities: machine learning-based decision-support tool - Liyang Huang; Liyuan Zhao; Zhi-Chun Li (Transportation Research Part D: Transport and Environment, 2026)

Integrated machine learning and density functional theory to design C₃N₅ piezo-catalysts toward precise control of selective reactive oxygen species and efficient water purification - Ting Li; Xianhu Long; Wei Liu; Fan Huang; Huinan Zhao; Tao Zhong; Jingyun Fang; Chun He (Journal of Hazardous Materials, 2026)

Large-scale REE mineralization linked to intensive evolution of carbonatitic-alkaline magmas to brine-melts: Insights from Sr-Nd-Ba isotopes - Xiao-Chun Li; Geng-Xin Deng; Xiao-Yun Nan; Xue-Yin Yuan; Hong-Rui Fan; Fang Huang (Geochemistry, 2026)

Elucidation of dynamic evolution patterns of non-volatile and volatile compounds in peel of Citrus reticulata cv. Chachiensis with different tree ages: a metabolomics-based analysis - Kexin Cao; Chun Yao; Jian Xiao; Rongshao Huang; Zutian Qin; Yusheng Shi; Jianhua Chen; Liangbo Li (Food Research International, 2026)

Carbon footprint portraits for multimodal trip chains in the context of Mobility as a Service - Chun Sheng; Jianan Cheng; Guo Wang; Ziyun Huang; Wenxiang Li (Environmental Impact Assessment Review, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Cardiovascular Risk and Prediction Model of Vascular Endothelial Growth Factor Tyrosine Kinase Inhibitors in Patients with Liver Cancer - Yen-Chou Chen; Chun-Yao Huang; Li-Ming Lien; Jin-Hua Chen; Bagas Suryo Bintoro; Fang-I Hsieh (Cardiovascular Toxicology, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

The bioaccumulation characteristics and combined toxicity effects of aged microplastics with adsorbed Hg(II) in oysters - Lianghong Li; Chun Lv; Qijia Zhou; Qiaoguo Tan; Haiying Lin; Qingge Feng; Xiaohong Song; Xianghua Wu; Qiuyan Hu; Lixin Huang; Jie He; Guanjian He; et al. (Journal of Hazardous Materials, 2026)

Insight into the influence of macerals on tar yield and components based on macro maceral separation of a tar-rich coal - Zeyu Peng; Qian Zhang; Le Li; Chun Han; Litong Liang; Zhihua Gao; Dong Wang; Yongming Xin; Wei Huang (Fuel, 2026)

Release characteristics and kinetic model of alkali metals during municipal solid waste incineration based on multipoint laser-induced breakdown spectroscopy - Nanxi Bie; Yongda Huang; Yi Huang; Shuai Li; Aijun Li; Hongyun Hu; Xian Li; Guangqian Luo; Chun Lou; Hong Yao (Fuel, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

The association between indoor VOCs exposure and lung function in adult asthma patients and the mediating effect of metabolites - Miao Yu; Dongxia Jiang; Ying Shang; Zhengxiong Li; Chun Chang; Shaodan Huang (Atmospheric Environment, 2026)

PbrRALF5/10 prevents incompatible pollen tube death by reconstructing the methyl-esterified pectin and reactive oxygen species metabolism of pear in vitro - Xiao-Xiong Kong; Tao Chen; Li-Yu Gao; Xu Huang; Xiao Liu; Jing Zhang; Zhi-Ping Zhang; Chun-Lei Wang (Plant Molecular Biology, 2026)

Meridional tripole hydroclimate pattern changes in East Asian monsoon region of China during the Younger Dryas - Wenyu Dong; Wanyin Qiu; Kui Gao; Yue Li; Xing Liu; Yan Yang; Yi Wang; Xianfeng Wang; Chun-Yuan Huang; Chuan-Chou Shen; Binggui Cai; Xiuyang Jiang (Quaternary Science Reviews, 2026)

Caseazins R−Y, cytotoxic podocarpane diterpenoids from Casearia kurzii - Xue-Wen Wu; Qiong Wei; Xia Pu; Chun-Mei Cha; Rui Li; Yin-Qiao Huang; Rui-Han Zhang; Xiao-Li Li; Hong-Liang Li; Wei-Lie Xiao (Phytochemistry, 2026)

Synergistic effect of the small VAWTs and large HAWTs for forced wake recovery of wind farm - Jiaxin Shen; Jian Chen; Chun Li; Ying Wang; Weijia Huang (Ocean Engineering, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Engineering a plasmonic Schottky heterojunction via in situ encapsulation of bismuth nanosheets in a metal-organic framework for efficient CO2 photoreduction - Deng-Yue Zheng; Ren-Feng Yang; Ziquan Li; Jinping Gao; Xiao-Hong Xiong; Mian Li; Xiao-Chun Huang (Chemical Engineering Journal, 2026)

Progresses in nucleate boiling studies and gaps between experimental works and real-world applications in in-vessel retention (IVR) - Zihao Wang; Yanxu Huang; Yunyu Qiu; Zhijiong Wang; Yuxin Tang; Yih-Min Wang; Hung-Chun Li; Kai Wang; Xiujie He (Annals of Nuclear Energy, 2026)

A 3D Lithospheric Thermal Model of the South China Sea Jointly Constrained by Heat Flow, Curie-Point Depth and S-Wave Velocity - Liang Huang; Chun-Feng Li; Zhaocai Wu; Jinyao Gao (Journal of Marine Science and Engineering, 2025)
In this study, we develop a 3D thermal model of the South China Sea (SCS) lithosphere through the joint analysis of heat flow, Curie-point depth derived from magnetic anomalies, and shear wave velocity. Results show the Moho temperature is below 250 °C in the oceanic basin but exceeds 350 °C in continental margins. We evaluate potential Moho drilling sites based on temperature, crustal thickness, water depth, and sediment thickness, identifying six favorable zones in the east sub-basin. The thermal lithosphere thickness correlates with tectonic settings in continental areas, while the oceanic lithosphere is thicker than predicted by theoretical models. Global analysis suggests that the slow spreading rate may have also contributed to the thickening of the oceanic lithosphere in the SCS.

A new method to predict seismic fragility of buried pipelines considering multiple failure modes - Zhao-Hui Lu; Ze-Shuo Kong; Chao-Huang Cai; Chun-Qing Li (Tunnelling and Underground Space Technology, 2025)

PcUGT203E1 and PcUGT203B2 are involved in abamectin susceptibility in Panonychus citri - Yuchao Shen; Zehao Huang; Sichen Li; Wanfu Yao; Liu Liu; Shijun Fu; Shijiang Yu; Binbin Shao; Lili Ding; Qiqi Yang; Yang Li; Shaohui Zhang; et al. (Pesticide Biochemistry and Physiology, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Cross-scale 3D visualization characterization and seepage simulation of pore structures in thermally desorbed diesel-contaminated soil - Zonghui Liu; Guangyuan Li; Yeyang Chun; Zheng Huang; Jiawei Qin (Computers and Geotechnics, 2025)

Ohmic contact interface engineering of fullerene-derived long-range ordered porous carbon-based anodes for durable sodium-ion capacitors - Jundong Shao; Mingming Gao; Ying Huang; Songlin Liu; Junke Li; Xiaosong Xiong; Antonio Gaetano Ricciardulli; Sheng Yang; Yubin Fu; Faxing Wang; Chun Fang; Panpan Zhang; et al. (Chemical Engineering Journal, 2025)

Novel self-assembled antimicrobial peptide Pardaxin hydrogel as a functional biomaterial for food packaging and preservation - Sanjay Prasad Selvaraj; Ju-Chun Chang; Karukuvelraja Raja; Jing-Ting Zhu; Prakash Kishore Hazam; Wen-Chun Lin; Jung-Ren Huang; Tsung-Lin Li; Jyh-Yih Chen (Chemical Engineering Journal, 2025)

Unleashing instant on-site naked-eye detection by a portable NIR-SPR platform with organic upconversion - Li-Chen Su; Xin-Hui Wang; Chun-Jen Shih; Zhi-Hao Huang; Ying-Feng Chang; Chen-Kai Chang; Chi-Yun Wang; Yu-Ching Huang; Shun-Wei Liu (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Unraveling the functional complexity of the locus coeruleus-norepinephrine system: insights from molecular anatomy to neurodynamic modeling - Chun-Wang Su; Fan Yang; Runchen Lai; Yanhai Li; Hadia Naeem; Nan Yao; Si-Ping Zhang; Haiqing Zhang; Youjun Li; Zi-Gang Huang (Cognitive Neurodynamics, 2025)

Tectonic deformation of the Mussau Trench and its implications for subduction initiation - Xueting Zhao; Chun-Feng Li; Liang Huang; Shuang Zhu; Yongkang Deng; Tao Wu; Dongdong Dong; Guoliang Zhang; Jiazheng Zhang; Yutao Liu; Yaqing Li; Fugui Tang; et al. (Acta Oceanologica Sinica, 2025)

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Polystyrene nanoplastics impair endometrial decidualization via cell cycle arrest and JNK-MAPK pathway-mediated oxidative stress in early pregnant mice - Jing-Ai Li; Li-Qing Wang; Qiong-Jun Xu; Xiao-Mei Wu; Xiao-Qing Pang; Jin-Xin He; Qian-Feng Qiao; Huang-Nian You; Yan-Chun Wu; Yong-Jiang Zhou (Food and Chemical Toxicology, 2025)

Constructing hollow CaO particles with abundant oxygen vacancies via co-adding Ce and Al to achieve superior CO2 capture performance in the calcium looping technique - Jian Chen; Haonan Huang; Jiacheng Yu; Feiqiang Chen; Wenhao Jin; Jiaze Sun; Youshi Li; Chun Zhu (Chemical Engineering Journal, 2025)

Deproteinization and controlled starch prehydrolysis in intact pulse cotyledon cells regulates starch retrogradation and digestion - Minghao Mao; Mario M. Martinez; Yunus Emre Tunçil; Li Ding; Chun Chen; Xiong Fu; Qiang Huang; Bin Zhang (Carbohydrate Polymers, 2025)

Molecular mechanisms and therapeutic application of pyrogallic acid in treating multidrug-resistant Klebsiella pneumoniae infections in American bullfrogs (Aquarana catesbeiana) - Han Lin; Furong Li; Yufang Huang; Yongping Ye; Ziyan Chen; Chun Liu; Ruiai Chen (Aquaculture, 2025)

Phytochrome B modulates arsenite stress tolerance and arsenic accumulation in rice (Oryza sativa L.) - Yimei Wang; Shuai Huang; Zongrun Li; Jundan Tong; Yile Sheng; Chun Ye; Weixu Huo; Yafan Zhao; Yanxiu Du; Ting Peng; Jing Zhang (Journal of Hazardous Materials, 2025)

Guidance disentanglement network for Optics-Guided thermal UAV image super-resolution - Zhicheng Zhao; Juanjuan Gu; Chenglong Li; Chun Wang; Zhongling Huang; Jin Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the stems of Daphniphyllum angustifolium Hutch. and their chemotaxonomic significance - Xiao-Juan Huang; Heng-Gang Zhang; Xiao-Hong Li; Yu-Bin Wei; Khalid-Hassan Mohamed; Chang-Qin Yin; Hao-Fei Yu; Cai-Feng Ding; Lan-Chun Zhang (Biochemical Systematics and Ecology, 2025)

Characteristics and mechanisms of summer long-lived heatwaves in Western North America: Perspective from Rossby wave train - Qian Qiang; Jian Shi; Jiajie Chen; Hengxing Qu; Yichuan Lu; Fei Huang; Chun Li; Saisai Ding (Atmospheric Research, 2025)

Impaired Synaptic Plasticity Mediated by Decreased GLUT1 in Hippocampal Astrocytes is Involved in Postoperative Cognitive Dysfunction in Elderly Mice - Zi-Yi Li; Qiang Liu; Xiao-Tian Shi; Xin-Hao Jiao; Yue Zhou; Chen Chen; Wei-Feng Wu; Wei Dong; Yong-Kang Qiu; Yi-Qi Liu; Chun-Hui Jin; Ao Sun; et al. (Molecular Neurobiology, 2025)

New 1,2,3-triazole-linked (±)-agrimonolide derivatives as anti-ulcerative colitis agents inhibiting JAK1/STAT3 pathways - Xiao Zhang; Ming-Qian Ju; Heng-Li Yang; Chun-Fei Zhang; Mao-Kui Huang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Influence of Varying Fractal Characteristics on the Dynamic Response of a Semi-Submersible Floating Wind Turbine Platform - Wanyong Zhang; Haoda Huang; Qingsong Liu; Yangtian Yan; Chun Li; Weipao Miao; Minnan Yue; Wanfu Zhang (Journal of Marine Science and Engineering, 2025)
Offshore wind turbines positioned in deepwater areas are increasingly favored due to them providing superior and stable wind resources. However, the dynamic stability of floating offshore wind turbines (FOWTs) under complex environmental loading remains challenging. This study proposes a novel semi-submersible platform featuring a fractal structure inspired by the venation of Victoria Amazonica and investigates the effects of fractal branching level and biomimetic structural height on platform motions, with the aim of enhancing the overall system stability of FOWTs. Within a high-fidelity computational fluid dynamics (CFD) framework coupled with a dynamic fluid–body interaction (DFBI) model and a volume-of-fluid (VOF) wave model, the dynamic responses of the biomimetic platform are investigated under varying fractal dimensions (Df) and structural heights. The results indicate that increasing fractal complexity enhances the local wall viscosity effect, significantly improving energy dissipation capabilities within the fractal cavities. Specifically, an eight-level fractal structure shows optimal performance, achieving reductions of approximately 16.94%, 23.26%, and 35.63% in heave, pitch, and rotational energy responses, respectively. Additionally, the increasing fractal height further strengthens energy dissipation, markedly enhancing stability, particularly in pitch motion. These findings underscore the substantial potential of biomimetic fractal designs in enhancing the dynamic stability of FOWTs.

In situ generation of Cu(III) synergized with crystalline amorphous strong interfacial interaction for autocatalytic degradation of LEV - Chun Zhang; Qin Chen; Yuxuan Li; Zhiyong Cai; Zhiguo Wang; Wei Huang; Peng Yu (Water Research, 2025)

Novel NLRP3 inhibitors mitigate acute radiation-induced lung injury by suppressing pyroptosis in alveolar epithelial cells - Yupeng Zhi; Huijia Chen; Yihao Huang; Lipeng Li; Zibin Chen; Hongzhao Huang; Fang Ke; Yansong Guo; Chun Chen (Toxicology and Applied Pharmacology, 2025)

Evolutionary history of a paleo-oxbow lake in the Yellow River within the Zoige Basin, NE Tibetan Plateau - Pengpeng Cao; Yuzhu Zhang; Yan Zhu; Ninglian Wang; Chun Chang Huang; Xiaohui Shi; Jiangli Pang; Yuqin Li; Jinpeng Zhou; Sikai Wang; Yao Jin; Mengting Li; et al. (Quaternary International, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Research progress on the directional breeding of function protein producing strain of edible fungi based on the nutritional proteomics - Nan Miao; Yuanchao Liu; Chun Xiao; Longhua Huang; Xiangmin Li; Manjun Cai; Wei Zhong; Huixiang Tian; Qinzhao Ruan; Shaodan Chen; Tianqiao Yong; Huiping Hu; et al. (Food Bioscience, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Phase and defect engineering of 1T/2H MoS2-x nanosheets for enhanced piezocatalytic inactivation of antibiotic-resistant bacteria - Huinan Zhao; Zhangnan Yao; Ting Li; Yanhong Lu; Kaiwen Wang; Jia He; Shuanghong Tian; Fan Huang; Chun He (Journal of Hazardous Materials, 2025)

Creep behavior of slip zone considering the rivalry between soil hardening and damage: case study of a giant colluvial landslide - Mengshuang Huang; Huiming Tang; Qinwen Tan; Zhiqiang Fan; Chun Li; Changdong Li; Yikai Niu; Zhongzhu Huang; Xuan Liu (Natural Hazards, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Establishment and characterization of a novel patient-derived TP63-rearranged anaplastic large-cell lymphoma model PTCL-S1 - Kelila Xin Ye Chai; Elizabeth Chun Yong Lee; Zhimei Li; Nur Ayuni Binte Muhammad; Jing Quan Lim; Dachuan Huang; Soon Thye Lim; Jason Yongsheng Chan; Choon Kiat Ong (Human Cell, 2025)
Anaplastic large-cell lymphoma (ALCL) accounts for 15% of all peripheral T-cell lymphomas globally and can be further divided into subcategories, of which patients with ALK-negative ALCL have dismal prognosis and overall survival. We established a patient-derived xenograft (PDX) and in vitro model (designated PTCL-S1) of TP63 -rearranged ALK-negative ALCL from the primary tumour site of a 55-year old Chinese woman. Whole genome sequencing of the patient’s tumour identified various mutations including AKT1 and NOTCH1 , as well as the TP63 - TBL1XR1 gene fusion. RNA sequencing followed by Sanger sequencing confirmed the gene rearrangement in original tumour, PDX and PTCL-S1 cell line. Immunohistochemistry profiling of the PDX model and cell-line were consistent with the patient’s primary tumour sample (CD3 + /CD30 + /CD79a-). Cytotoxic agents (doxorubicin, etoposide and gemcitabine) commonly used in ALCL treatment exhibited potent anti-proliferative activity in the cell-line. In conclusion, the established PTCL-S1 cell line can be a useful tool for further investigation of the understanding of TP63 -rearranged ALK-negative ALCL.

Three new polyketide metabolites from the endophytic fungus Trichoderma protrudens of Hibiscus tiliaceus - Yan-Mei Wu; Jing-Ya Mo; Yong-Yan Mei; Quan Liu; Yuan-Yuan Huang; Bei Zhou; Yi-Hang Li; Yan-Chun Wu; Jing-Quan Yuan (Phytochemistry Letters, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Nuclear translocation of β-catenin and migration of arecoline-induced oral cancer cells reduced by Taiwanin E via p-GSK3β downregulation - Chi-Cheng Li; Marthandam Asokan Shibu; Wei-Wen Kuo; Yueh-Hsiung Kuo; Yun-Peng Chao; Chun-Hsu Yao; Da-Tian Bau; Pei-Jei Lio; Chung-Jen Chiang; Chih-Yang Huang (Molecular & Cellular Toxicology, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Development of in-situ MOF-modified ceramic filters for enhancing fluoride removal in water supply for remote communities - Yifei Luo; Guohe Huang; Yongping Li; Jing Huang; Yao Yao; Peng Zhang; Zixin Zhang; Jian Shen; Jianan Yin; Xiujuan Chen; Yuwei Wu; Mengna Li; et al. (Journal of Environmental Management, 2025)

Impact of agricultural straw open-field burning on concentrations of six criteria air pollutants in China - Hao-Neng Huang; Zhou Yang; Yuming Guo; Jia-Jun Ma; Bo-Wen Ming; Jun Yang; Cui Guo; Li Li; Chun-Quan Ou (Environmental Pollution, 2025)

ZnAl alloy and organosulfur hybrid energy storage for long term cyclability - Qing Liu; Zhiyong Zheng; Chun Huang; Gun Jang; Qingyun Dou; Yong Li; Shengyang Huang; Baohuai Zhao; Yongan Wu; Yi Zhang; Bo-Kyong Kim; Xu Yu; et al. (Chemical Engineering Journal, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Scavenging contributes to larval food intake in fungus gnats using the Arisaema kettle trap as a brood site - Wen Huang; Xin Li; Qing‐Feng Wang; Chun‐Feng Yang; Jon Ågren (Ecology, 2025)

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

High-Precision Sub-Seafloor Velocity Building Based on Joint Tomography and Deep Learning on OBS Data in the South China Sea - Guoxin Chen; Jun Li; Jinxin Chen; Rongsen Du; Yutao Liu; Yuli Qi; Chun Feng Li; Xingguo Huang (Journal of Earth Science, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Pathological and biochemical effects of polyethylene microplastic exposure in hydrothermal vent crab, Xenograpsus testudinatus - Mark June S. Consigna; Li-Chun Tseng; Chi Chou; Ching-Wen Huang; Yi-Ta Shao; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Study on the nutritional relationships in mycelia and fruiting bodies of Hypsizygus marmoreus under defined nutrient conditions - Jianqiu Chen; Mingming Yu; Chun Yang; Zenan Huang; Lizhang He; Jiaojiao Bian; Shujing Sun; Jiahuan Li (Food Chemistry, 2025)

Polystyrene microplastics induce hepatic lipid metabolism and energy disorder by upregulating the NR4A1-AMPK signaling pathway - Hui-Wen Chiu; Chun-Wei Chu; Chih-Chia Huang; Zi-Chun Chia; Yung-Li Wang; Yu-Hsuan Lee (Environmental Pollution, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Formation ages and environmental conditions of paleo-periglacial involutions in the Yellow River source area, northeastern Tibetan Plateau - Yao Jin; Yuzhu Zhang; Ninglian Wang; Chun Chang Huang; Jiangli Pang; Yan Zhu; Longsheng Wang; Mengting Li; Sikai Wang; Pengpeng Cao; Qili Xiao; Jinpeng Zhou; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

NLRP3 inflammasome mediates pyroptosis of alveolar macrophages to induce radiation lung injury - Mingwei Zhang; Hailin Lan; Meina Jiang; Minghuan Yang; Hongquan Chen; Shaoli Peng; Xuezhen Wang; Yarui Zhang; Xingxin Huang; Lianhuang Li; Chun Chen; Jinsheng Hong (Journal of Hazardous Materials, 2025)

Dual Channel passivation enhancing stable perovskite Light-Emitting diodes - Shao-Qi Wang; Wei Yang; Yu Xia; Bin Wang; Nan Li; Lei Huang; Xin Chen; Yu-Han Li; Jing Chen; Chun-Hao Chen; Zhao-Kui Wang (Chemical Engineering Journal, 2025)

The trojan horse strategy in T-ALL therapy by engineering T-ALL-derived exosomes for targeted delivery of Isoliquiritigenin to the bone marrow to conquer Drug-Resistant T-ALL in PDX model - Yong Liu; Lindi Li; Cheng Ouyang; Zefan Du; Su Liu; Hailin Zou; Chunmou Li; Junbin Huang; Yucai Cheng; Mengyao Tian; Tianwen Li; Jiani Mo; et al. (Chemical Engineering Journal, 2025)

Effect of ambient ozone and its interactions with ambient PM2.5 and temperature on peak expiratory flow in adults with asthma - Dongxia Jiang; Ying Shang; Zhengxiong Li; Xianlin Mu; Xuehu Han; Xinzhuo Xie; Guanglong Fu; Yunshu Zhang; Shaodan Huang; Chun Chang (Atmospheric Environment, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Prevalence of common upper gastrointestinal diseases in Chinese adults aged 18–64 years - Hong Yang; Mei Zhang; Hui Li; Zhengjing Huang; Yuanyuan Sun; Wenbo Li; Chun Li; Xuzhen Qin; Yanhong Wang; Xiao Zhang; Zhenping Zhao; Limin Wang; et al. (Science Bulletin, 2024)

Provenance geochemical detection of soil deposits from archaeological limestone caves in the Bubing Basin, tropical China - Wei Liao; Chun Tian; Hua Liang; Yanyan Yao; Jinyan Li; Yuan Yan; Shengmin Huang; Christopher J. Bae; Wei Wang (Quaternary International, 2024)

“Nano knife” for efficient piezocatalytic inactivation of amoeba spores and their intracellular bacteria: Synergetic effect between physical damage and chemical oxidation - Huinan Zhao; Jianyi Zheng; Wei Huang; Zhenzhen He; Fan Huang; Lin Zhang; Tao Zhong; Yadi Li; Dehua Xia; Longfei Shu; Chun He (Journal of Hazardous Materials, 2024)

Roles of direct and indirect photodegradation in the photochemical fates of three 3rd generation fluoroquinolones - Yitao Li; Jason Chun Ho Lam; Yuhe He; Yuefei Ruan; Xinming Huang; Theodora Nah (Journal of Hazardous Materials, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Hydrology controls sulfuric acid-mediated weathering in an orogenic regime of southwestern Taiwan - Hou-Chun Liu; Meng-Xuan Li; Chen-Feng You; Yan-Hong Chen; Kuo-Fang Huang; Chuan-Hsiung Chung; Guan-Wei Lin (Science of The Total Environment, 2024)

Updates on infectious diseases of largemouth bass: A major review - Shun Yang; Jing Zhao; Nan An; Dong-Chun Li; Meng-Meng Huang; Hui Fei (Fish & Shellfish Immunology, 2024)

Mechanisms and valorization of selective adsorption of Sb(III) by amino-functionalized lignin-based porous biochar - Wei Huang; Zhixuan Yang; Junguang Hu; Xin Chen; Wei Li; Zhiguo Wang; Chun Zhang; Qiongchao Wang; Xinxin Xiao; Peng Yu (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Micromorphological characteristics and environmental significance of the Holocene aeolian loess-paleosol section in the Zoige Basin - Dou Chen; Jiangli Pang; Yuzhu Zhang; Chun Chang Huang; Yali Zhou; Xiaochun Zha; Yuqin Li; Qili Xiao; Xiaokang Zhao (CATENA, 2024)

Phytochemical constituents from rhizomes of Dryopteris crassirhizoma and their anti-inflammatory activity - Xiao-Jun Li; Xiong-Hui Song; Si-Qi Tang; Kai-Xin Wei; Zong-Wu Suo; Yi Xu; Jiao Luo; Hao Huang; Chun-Ying Li; Dong-Xu Liu; Xiang-Qian Liu (Natural Product Research, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Treatment of swine manure by hydrothermal carbonization: The influential effect and preliminary mechanism of surfactants - Zhen-tian Feng; Jiang-bo Xiong; Guo-feng Wang; Lin Li; Chun-fei Zhou; Chun-huo Zhou; Hua-jun Huang (Science of The Total Environment, 2024)

Joint effects of air pollution and genetic susceptibility on incident primary open-angle glaucoma - Hao-Neng Huang; Pan-Pan Zhu; Zhou Yang; Yi-Ming Tao; Xiaofeng Ma; Hai-Bing Yu; Li Li; Chun-Quan Ou (Science of The Total Environment, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Signal characteristics and energy transmittance during detonation tube excitation in a gas–water–soil environment - Hai-cheng Lv; Ning Li; Xiao-long Huang; Cheng Li; Chun-sheng Weng (Ocean Engineering, 2024)

MOF-derived carbon supporting tubular In2O3 for efficient photocatalytic degradation of antibiotics - Yilin Pan; Kaizhou Huang; Beijia Lin; Xiang Li; Chun Hu; Zhihong Chen; Peng Zhang (Journal of Environmental Chemical Engineering, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Dual-Functional group passivation to foster buried interface Cohesion for High-Performance perovskite photovoltaics - Namatullah Nizamani; Kai-Li Wang; Run-Jun Jin; Chun-Hao Chen; Jing Chen; Yu Xia; Lei Huang; Yu-Han Li; Mary Donnabelle Balela; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Simultaneous carbon, nitrogen and phosphorus removal in sequencing batch membrane aerated biofilm reactor with biofilm thickness control via air scouring aided by computational fluid dynamics - Chun-Hai Wei; Xin-Yu Zhai; Yu-Duo Jiang; Hong-Wei Rong; Li-Gong Zhao; Peng Liang; Xia Huang; Huu Hao Ngo (Bioresource Technology, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Development and Application of an Advanced Automatic Identification System (AIS)-Based Ship Trajectory Extraction Framework for Maritime Traffic Analysis - I-Lun Huang; Man-Chun Lee; Li Chang; Juan-Chen Huang (Journal of Marine Science and Engineering, 2024)
This study addresses the challenges of maritime traffic management in the western waters of Taiwan, a region characterized by substantial commercial shipping activity and ongoing environmental development. Using 2023 Automatic Identification System (AIS) data, this study develops a robust feature extraction framework involving data cleaning, anomaly trajectory point detection, trajectory compression, and advanced processing techniques. Dynamic Time Warping (DTW) and the Hierarchical Density-Based Spatial Clustering of Applications with Noise (HDBSCAN) algorithms are applied to cluster the trajectory data, revealing 16 distinct maritime traffic patterns, key navigation routes, and intersections. The findings provide fresh perspectives on analyzing maritime traffic, identifying high-risk areas, and informing safety and spatial planning. In practical applications, the results help navigators optimize route planning, improve resource allocation for maritime authorities, and inform the development of infrastructure and navigational aids. Furthermore, these outcomes are essential for detecting abnormal ship behavior, and they highlight the potential of route extraction in maritime surveillance.

Synthesis of Cu/Mn bimetallic organic framework material and their catalytic performance for NH3-SCR - Wei Dong; Fuping Qian; Shian Zhou; Shenghua Wu; Qingda Gao; Tiejun Chun; Lei Ding; Hong-ming Long; Gang Li; Naijin Huang (Journal of Cleaner Production, 2024)

Spatial variation, emissions, transport, and risk assessment of organophosphate esters in two large petrochemical complexes in southern China - Wen-Qing Mo; Zhen-Shan Huang; Qi-Qi Li; Jun Yao; Chun-You Zhu; Hui-Ying Guo; Yuan Zeng; She-Jun Chen (Journal of Environmental Management, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

BM-RCWTSG: An integrated matching framework for electric vehicle ride-hailing services under stochastic guidance - Xiaoming Li; Hubert Normandin-Taillon; Chun Wang; Xiao Huang (Sustainable Cities and Society, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Screening and effects of intestinal probiotics on growth performance, gut health, immunity, and disease resistance of Nile tilapia (Oreochromis niloticus) against Streptococcus agalactiae - Xinzhi Huang; Huanrong He; Zehong Li; Chun Liu; Biao Jiang; Yanhua Huang; Youlu Su; Wei Li (Fish & Shellfish Immunology, 2024)

Long-term reduced and no tillage increase maize (Zea mays L.) grain yield and yield stability in Northeast China - Yan-Jie Lv; Xiao-Long Zhang; Lei Gong; Shou-Bing Huang; Bao-Long Sun; Jin-Yu Zheng; Yong-Jun Wang; Li-Chun Wang (European Journal of Agronomy, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

MicroRNA miR-145-5p Inhibits Cutaneous Wound Healing by Targeting PDGFD in Diabetic Foot Ulcer - Chun Wang; Li Huang; Juan Li; Dan Liu; Biaoliang Wu (Biochemical Genetics, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

What controls the magma production rate along the Walvis Ridge, South Atlantic? - Liang Huang; Chun-Feng Li (Tectonophysics, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Molecular mechanism for the unusual enhancement of the second-step chemiluminescence production from the carcinogenic tetrabromohydroquinone and H2O2 - Zi-Han Wang; Chun-Hua Huang; Zhi-Sheng Liu; Li Mao; Ben-Zhan Zhu (Journal of Environmental Sciences, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Ultrathin Sn-doped Ga2O3 for power field-effect transistors: Si-compatible 4-inch array with high-k gate dielectric - Zi-Chun Liu; Jia-Cheng Li; Hui-Xia Yang; Han Yang; Yuan Huang; Yi-Yun Zhang; Pui-To Lai; Yuan-Xiao Ma; Ye-Liang Wang (Science Bulletin, 2024)

The De underestimation caused by the unstable medium component in the initial OSL signal from lava-baked quartz and correction strategies - Chun-Xin Wang; Chang Huang; Anchuan Fan; Sheng-Hua Li (Quaternary Geochronology, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Natural and engineered enzymes for polyester degradation: a review - Rey-Ting Guo; Xian Li; Yu Yang; Jian-Wen Huang; Panpan Shen; Rock Keey Liew; Chun-Chi Chen (Environmental Chemistry Letters, 2024)
Plastic pollution is becoming a major health issue due to the recent discovery of microplastics and nanoplastics in living organisms and the environment, calling for advanced technologies to remove plastic waste. Here we review enzymes that degrade plastics with focus on plastic properties, protein engineering and polymers such as poly(ethylene terephthalate), poly(butylene adipate-co-terephthalate), poly(lactic acid), polyamide and polyurethane. The mechanism of action of natural and engineered enzymes has been probed by experimental and computation approaches. The performance of polyester-degrading enzymes has been improved via directed evolution, structure-guided rational design and machine learning-aided strategies. The improved enzymes display higher stability at elevated temperatures, and tailored substrate-binding sites.

Automatic offline-capable smartphone paper-based microfluidic device for efficient biomarker detection of Alzheimer's disease - Sixuan Duan; Tianyu Cai; Fuyuan Liu; Yifan Li; Hang Yuan; Wenwen Yuan; Kaizhu Huang; Kai Hoettges; Min Chen; Eng Gee Lim; Chun Zhao; Pengfei Song (Analytica Chimica Acta, 2024)

Association between ambient temperature and mammalian-related injuries in Guangzhou, China, 2014–2019 - Jia-Jun Ma; Ze-Jie Xu; Boheng Liang; Zhou Yang; Li Li; Hao-Neng Huang; Bo-Wen Ming; Pengzhe Qin; Chun-Quan Ou (Science of The Total Environment, 2024)

Structural, functional properties, and in vitro digestibility of sunflower protein concentrate as affected by extraction method: Isoelectric precipitation vs ultrafiltration - Xiaoling Huang; Yi Li; Chun Cui; Dongxiao Sun-Waterhouse (Food Chemistry, 2024)

Bio-based adsorption foam composed of MOF and polyethyleneimine-modified cellulose for selective anionic dye removal - Zihui Yuan; Feng Li; Xuefeng Zhang; Mei-Chun Li; Yan Chen; Cornelis F. de Hoop; Jinqiu Qi; Xingyan Huang (Environmental Research, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

An oxygen isotope perspective on the break-up of the Rodinia supercontinent - Hao Zou; Chang-Cheng Huang; Hua-Wen Cao; Chun-Mei Liu; Hui-Dong Yu; Franco Pirajno; Xian-Hua Li (Earth-Science Reviews, 2024)

A multi-functional CoN-Mo2N heterostructure nanorods for high performance lithium-sulfur batteries - Chun Xu; Xiangli Jiang; Minggang Huang; Wei Luo; Shan Zhang; Shuo Zhao; Guochun Li; Jiabiao Lian (Chemical Engineering Journal, 2024)

Reshaped buried interface by comprehensive passivation for highly efficient perovskite photovoltaics - Lei Huang; Kai-Li Wang; Run-Jun Jin; Jing Chen; Chun-Hao Chen; Yu Xia; Yan-Hui Lou; Zhao-Kui Wang (Chemical Engineering Journal, 2024)

Immediate and delayed effects of environmental temperature on schizophrenia admissions in Liuzhou, China, 2013–2020: a time series analysis - Qian Zhou; Xiaolan Huang; Li Su; Xianyan Tang; Yanli Qin; Yuting Huo; Chun Zhou; Jun Lan; Yue Zhao; Zaifei Huang; Guoguang Huang; Yuhua Wei (International Journal of Biometeorology, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Study on the mechanism and stability of microbially induced struvite precipitation (MISP) for enhanced immobilization of uranium - Yao-ting Duan; Xin Xu; Lei Niu; Zhe Wang; Xiao-gang Huang; Chun-li Zheng (Journal of Cleaner Production, 2024)

Determination of the Elemental Iodine in Human Breast Milk by Inductively Coupled Plasma mass Spectrometry - Chun-Jui Huang; Jia-Zhen Li; Chii-Min Hwu; Harn-Shen Chen; Chang-Ching Yeh; Fan-Fen Wang; Chen-Chang Yang (Biological Trace Element Research, 2024)

Proteomic characteristics of the treatment trajectory of patients with COVID-19 - Xue Li; Guilan Ding; Shilin Li; Chun Liu; Xiangde Zheng; Jinliang Luo; Sichun He; Fanwei Zeng; Xuan Huang; Fanxin Zeng (Archives of Virology, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

A novel defensin‐like peptide C‐13326 possesses protective effect against multidrug‐resistant Aeromonas schubertii in hybrid snakehead ( Channa maculate ♀ × Channa argus ♂) - Huanrong He; Xinzhi Huang; Caiyi Wen; Chun Liu; Biao Jiang; Yanhua Huang; Youlu Su; Wei Li (Journal of Fish Diseases, 2024)
The purpose of this study was to investigate whether a defensin‐like antimicrobial peptide (C‐13326 peptide) identified in Hermetia illucens could possess protective effect against multidrug‐resistant Aeromonas schubertii in hybrid snakehead ( Channa maculate ♀ × Channa argus ♂). The cDNA of C‐13326 peptide comprised 243 nucleotides encoding 80 amino acids, with six conserved cysteine residues and the classical CSαβ structure. The recombinant expression plasmid pPIC9K‐C‐13326 was constructed and transformed into GS115 Pichia pastoris , and the C‐13326 peptide was expressed by induction with 1% methanol. The crude extract of C‐13326 peptide was precipitated by ammonium sulfate, assayed by Braford method, detected by tricine‐SDS‐PAGE, evaluated by BandScan software and identified by liquid chromatography‐mass spectrometry. The C‐13326 peptide was shown to have inhibitory activity against the growth of multidrug‐resistant A. schubertii DM210910 by using the minimum growth inhibitory concentration and Oxford cup method. In addition, scanning electron microscopy analysis suggested that C‐13326 peptide inhibited the growth of A. schubertii DM210910 by damaging the bacterial cell membrane. To explore the role of peptide C‐13326 in vivo, hybrid snakehead was fed with peptide C‐13326 as feed additives for 7 days. The results revealed that C‐13326 peptide could significantly down‐regulate the expression levels of IL‐1β , IL‐8 , IL‐12 and TNF‐α ( p A. schubertii DM210910. Therefore, the C‐13326 peptide is a promising antimicrobial agent for A. schubertii treatment in aquaculture.

The effect of the mitochondria-targeted antioxidant Mito-tempo during sperm ultra-rapid freezing - Chun-Yuan Li; Juan Liu; Qi-Yuan Zheng; Nian Liu; Xi-Ling Huang; Yu-Yin Wu; Xing-Feng Yao; Qing-Ying Tan; Ying Huang; Chuan-Huo Hu; Chang-Long Xu (Cryobiology, 2024)

Unprecedented sulfenic acid-dependent hydroxyl radical production and DNA damage by N-heterocyclic thiols and H2O2 - Li Mao; Zhi-Sheng Liu; Chun-Hua Huang; Tian-Shu Tang; Hao-Zhe Zhang; Shi-Yu Chen; Ben-Zhan Zhu (Chemical Engineering Journal, 2024)

Effect of land use conversion on the soil aggregate-associated microbial necromass carbon in estuarine wetland of the Pearl River in China - Chun Liu; Zhinan Wu; Chunhuan He; Bin Huang; Yuheng Zhang; Ping Li; Weijia Huang (CATENA, 2024)

A Fluorescence Biosensor Based on Carbon Quantum Dots Prepared from Pomegranate Peel and T-Hg2+-T Mismatch for Hg2+ Detection - Weiqin Zhao; Chun Huang; Xiyu Guo; Youyu Zhu; Yuangang Li; Yingfeng Duan; Jie Gao (Journal of Fluorescence, 2024)

o-phenylenediamine Derived Fluorescent Carbon Quantum dots for Detection of Hg(II) in Environmental Water - Anqi Hu; Guoqing Chen; Anlan Huang; Zicheng Cai; Taiqun Yang; Chaoqun Ma; Lei Li; Hui Gao; Jiao Gu; Chun Zhu; Yamin Wu; Xiaoqian Qiu; et al. (Journal of Fluorescence, 2024)

Investigation of the Application and Mechanism of Nitrogen and Phosphorus Co-doped Carbon Dots for Mercury Ion Detection - Dong Yang; Chaoqun Ma; Guoqing Chen; Lei Li; Anqi Hu; Anlan Huang; Yan zhou; Zicheng Cai; Taiqun Yang; Hui Gao; Jiao Gu; Chun Zhu; et al. (Journal of Fluorescence, 2024)

Neglected negative effect of carbon quantum dots (CQDs) entering the ocean on marine organisms living in different water layers - Xinyang Li; Ciara Chun Chen; Lin Wu; Jin Zhou; Yuxiong Huang; Xiaoshan Zhu (Marine Pollution Bulletin, 2024)

Exploring the role of Maillard reaction and lipid oxidation in the advanced glycation end products of batter-coated meat products during frying - Yanxia Liu; Chun Liu; Xiaoshu Huang; Miaoyun Li; Gaiming Zhao; Lingxia Sun; Jiahuan Yu; Wei Deng (Food Research International, 2024)

Fluorinated polymer additives in Spiro-OMeTAD to improve the efficiency and stability of perovskite solar cells - Grace Dansoa Tabi; Dang-Thuan Nguyen; Wensheng Liang; Wenzhong Ji; Teng Lu; Thành Trần-Phú; Olivier Lee Cheong Lem; Azul Osorio Mayon; Keqing Huang; Li-Chun Chang; Hualin Zhan; Viqar Ahmad; et al. (Chemical Engineering Journal, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Comparison of the driving mechanism between logistics land use and facilities: A case study from Wuhan metropolitan area - Liyuan Zhao; Cong Zhou; Kaili Liu; Liyang Huang; Zhi-chun Li (Journal of Transport Geography, 2024)

Isolation and characterization of Bacillus cereus bacteriophage DZ1 and its application in foods - Zhichao Huang; Xiaoming Yuan; Zhenjun Zhu; Ying Feng; Na Li; Shubo Yu; Chun Li; Bo Chen; Shi Wu; Qihui Gu; Jumei Zhang; Juan Wang; et al. (Food Chemistry, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Elucidating influences of defects and thermal treatments on CO2 capture of a Zr-based metal–organic framework - Shan He; Ling-Xiao Li; Li-Tian Zhang; Shanshan Zeng; Chunmei Feng; Xiao-Xian Chen; Hao-Long Zhou; Xiao-Chun Huang (Chemical Engineering Journal, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

C4 leaf development and evolution - Chi-Fa Huang; Wen-Yu Liu; Chun-Ping Yu; Shu-Hsing Wu; Maurice S.B. Ku; Wen-Hsiung Li (Current Opinion in Plant Biology, 2023)

Industrial and agricultural waste amendments interact with microorganism activities to enhance P availability in rice-paddy soils - Zhuang Huang; Xiaoqing Zhang; Josep Peñuelas; Jordi Sardans; Qiang Jin; Chun Wang; Liuming Yang; Yunying Fang; Zimin Li; Weiqi Wang (Science of The Total Environment, 2023)

Amino-terminated carbon dots for imaging Golgi apparatus polarity in live cells - Lei Zhan; Peng Hou; Na Chen; Yuan Fang Li; Chun Mei Li; Cheng Zhi Huang (Chemical Engineering Journal, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Microbial communities and mineral assemblages in sediments from various habitats at the Haima Cold Seep, South China Sea - Jianzhen Liang; Jing-Chun Feng; Jie Kong; Yongji Huang; Hui Zhang; Song Zhong; Li Tang; Si Zhang (Frontiers in Marine Science, 2023)
Cold seeps create diverse habitats in the deep sea and play an important role in the global carbon cycling. Anaerobic oxidation of methane (AOM) and biogenic mineralization are essential carbon pathways of methane and carbon transformation in cold seeps, however, the effects of habitat heterogeneity on the processes are still poorly understood. In this study, we investigated the microbial communities and mineral assemblages at distinct habitats in the Haima cold seep and their relationships with environmental factors. These habitats were classified as methane seep site (MS), seep-free faunal habitat (FH), and control site (CS). Bacterial communities were significantly different among the three habitats. ANME-3 archaea, Sulfurovum bacteria, and mineralization-associated microbes (e.g., Campylobacterales) were detected in high relative abundances at ROV2. Mineralogical analysis revealed abundant calcite minerals at the seep site, indicating that authigenic carbonate minerals were formed at highly active seep. Multivariate statistical analysis demonstrated that the concentrations of SO 4 2– , Ca 2+ , and Mg 2+ were significantly correlated with the presence of calcite minerals and bacterial communities. These results suggested that AOM-accompanied authigenic carbonate formation is an important factor influencing the mineral assemblages in seep habitats. This finding improves our understanding of marine microbial carbon cycling.

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Mechanistic study of cytochrome P450 enzyme-mediated cytotoxicity of psoralen and isopsoralen - Shuaishuai Chen; Weiyu Guo; Huan Liu; Jiang Zheng; Dingyan Lu; Jia Sun; Chun Li; Chunhua Liu; Yonglin Wang; Yong Huang; Wen Liu; Yongjun Li; et al. (Food and Chemical Toxicology, 2023)

Rational design of genotyping nanodevice for HPV subtype distinction - De Yu Li; Yong Jian Jiang; Kun Han Nie; Jing Li; Yuan Fang Li; Cheng Zhi Huang; Chun Mei Li (Analytica Chimica Acta, 2023)

Variations in trihalomethane formation potential of Microcystis aeruginosa under different growth conditions: Phenomenon and mechanism - Rui Huang; Wenbo Guo; Zhiquan Liu; Shugeng Li; Zhiwei Zhao; Wenxin Shi; Fuyi Cui; Chun Hu (Science of The Total Environment, 2023)

Efficient immobilization and detoxification of gaseous elemental mercury by nanoflower/rod WSe2/halloysite composite: Performance and mechanisms - Xuelei Duan; Yuan Li; Changxian Zhao; Yiwen Shen; Qi Guo; Zhihao Huang; Dexu Shan; Yue Gao; Kegang Zhang; Jianbo Shi; Jingfu Liu; Yongsheng Chen; et al. (Journal of Hazardous Materials, 2023)

Cryo-EM structure and rational engineering of a superefficient ochratoxin A-detoxifying amidohydrolase - Longhai Dai; Du Niu; Jian-Wen Huang; Xian Li; Panpan Shen; Hao Li; Zhenzhen Xie; Jian Min; Yumei Hu; Yu Yang; Rey-Ting Guo; Chun-Chi Chen (Journal of Hazardous Materials, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

An advanced CoNb2O6 anode material with in-situ interstitial doping for high-rate lithium-ion batteries - Shuo Zhao; Ting Chen; Hongping Li; Yuanfeng Liu; Minggang Huang; Chun Xu; Yingxue Cui; Guochun Li; Jiabiao Lian; Yong Wang (Chemical Engineering Journal, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Treatment of diluted palm oil mill effluent (POME) synchronous with electricity production in a persulfate oxidant-promoted photocatalytic fuel cell - Chun-Ting Joyee Yap; Sze-Mun Lam; Jin-Chung Sin; Honghu Zeng; Haixiang Li; Liangliang Huang; Hua Lin (Environmental Science and Pollution Research, 2023)

Mechanism of aconitine mediated neuronal apoptosis induced by mitochondrial calcium overload caused by MCU - Chen Jiang; Jun Shen; Chun Wang; Yongjie Huang; Linbo Wang; Yiran Yang; Wen Hu; Ping Li; Haiying Wu (Toxicology Letters, 2023)

The future for biochemical recycling of poly(ethylene terephthalate): From lab to process - Chun-Chi Chen; Xian Li; Panpan Shen; Yunyun Yang; Jian Min; Qi Zhang; Yingle Liu; Jian-Wen Huang; Rey-Ting Guo (Current Opinion in Green and Sustainable Chemistry, 2023)

Genetic characteristics of a novel HIV-1 recombinant lineage (CRF103_01B) and its prevalence in northern China - Man Dai; Jia Li; Jie Li; Hongyan Lu; Chun Huang; Shiyun Lv; Huihuang Huang; Ruolei Xin (Virus Genes, 2023)

Association between greenspace and cancer: evidence from a systematic review and meta-analysis of multiple large cohort studies - Jiang Li; Yafei Xie; Jianguo Xu; Chun Zhang; Huilin Wang; Danqi Huang; Guoqiang Li; Jinhui Tian (Environmental Science and Pollution Research, 2023)

Mechanistic investigation of the differential synergistic neurotoxicity between pesticide metam sodium and copper or zinc - Chen Shen; Zhi-Guo Sheng; Jie Shao; Miao Tang; Li Mao; Chun-Hua Huang; Zhi-Hui Zhang; Ben-Zhan Zhu (Chemosphere, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Peak extraction and classification from digital elevation models based on the relationship between morphological characteristics and spatial position - Ming-wei Zhao; Yue Fang; Can-can Yang; Xiao-xiao Ju; Xiao-li Huang; Ling Jiang; Chun Wang; Yan Xu (Journal of Mountain Science, 2023)

Homogeneous/heterogeneous metal-catalyzed persulfate oxidation technology for organic pollutants elimination: A review - Bingzhi Liu; Baorong Huang; Zizeng Wang; Lei Tang; Changhao Ji; Chun Zhao; Li Feng; Yong Feng (Journal of Environmental Chemical Engineering, 2023)

In Silico Genome-Wide Mining and Analysis of Terpene Synthase Gene Family in Hevea Brasiliensis - Jiahao Liang; De Wang; Xin Li; Weiwen Huang; Chun Xie; Minghui Fu; Hongmei Zhang; Qiong Meng (Biochemical Genetics, 2023)

Effect of different doses of trichloroisocyanuric acid on aquaculture pond water - Hong-yu Zhang; Ying Huang; Ning Ma; Hai-bo Wang; Xiao-yong Zhang; Ying-chun Xing; Lei Xia; Guang Yang; Li-lai Yuan; Ying-ren Li (Aquaculture, 2023)

Generation mechanism of singlet oxygen from the interaction of peroxymonosulfate and chloride in aqueous systems - Anna Wang; Ben-Zhan Zhu; Chun-Hua Huang; Wei-Xian Zhang; Mengye Wang; Xuchun Li; Li Ling; Jun Ma; Jingyun Fang (Water Research, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Volatile-char interactions during biomass pyrolysis: Effect of biomass acid-washing pretreatment - Yao Wang; Bin Li; Anjiang Gao; Kuan Ding; Xie Xing; Juntao Wei; Yong Huang; Jason Chun-Ho Lam; K.A. Subramanian; Shu Zhang (Fuel, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Community assemblages and species coexistence of prokaryotes controlled by local environmental heterogeneity in a cold seep water column - Yongji Huang; Jing-Chun Feng; Jie Kong; Liwei Sun; Mingrui Zhang; Yanyan Huang; Li Tang; Si Zhang; Zhifeng Yang (Science of The Total Environment, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Hourly personal temperature exposure and heart rate variability: A multi-center panel study in populations at intermediate to high-risk of cardiovascular disease - Hongfan Li; Han Ma; Jinyue Li; Xiahua Li; Keyong Huang; Jie Cao; Jianxin Li; Weili Yan; Xiaotian Chen; Xiaoyang Zhou; Chun Cui; Xianglai Yu; et al. (Science of The Total Environment, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

14-3-3ζ Mediates GABAAR Activation by Interacting with BIG1 - Cuixian Li; Shen Huang; Jin Peng; Tianguo Hong; Chun Zhou; Jie Tang (Molecular Neurobiology, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

A novel one-pot strategy to construct 3D-printable cellulose nanofiber/poly(deep eutectic solvent) conductive elastomers - Shaoning Wang; Lili Zhang; Ruoteng Ma; Juan Yu; Xiya Zhang; Chun Shi; Lisha Ma; Tianqi Li; Yuefeng Huang; Yanlei Hu; Yimin Fan; Zhiguo Wang (Chemical Engineering Journal, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

A refined Moho depth model from a joint analysis of gravity and seismic data of the South China Sea basin and its tectonic implications - Liang Huang; Yonglin Wen; Chun-Feng Li; Xi Peng; Zhezhe Lu; Liuna Xu; Yongjian Yao (Physics of the Earth and Planetary Interiors, 2023)

Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy - Chun-Yin Huang; Haw-Wen Chen; Chia-Wen Lo; Yu-Ru Wang; Chien-Chun Li; Kai-Li Liu; Chong-Kuei Lii (Food and Chemical Toxicology, 2023)

Bioinspired, stable adhesive Ti3C2Tx MXene-based coatings towards fire warning, smoke suppression and VOCs removal smart wood - Yin Zhang; Yanping Huang; Mei-Chun Li; Shuai Zhang; Weimin Zhou; Changtong Mei; Mingzhu Pan (Chemical Engineering Journal, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Scaling-up and proteomic analysis reveals photosynthetic and metabolic insights toward prolonged H2 photoproduction in Chlamydomonas hpm91 mutant lacking proton gradient regulation 5 (PGR5) - Peng Liu; De-Min Ye; Mei Chen; Jin Zhang; Xia-He Huang; Li-Li Shen; Ke-Ke Xia; Xiao-Jing Xu; Yong-Chao Xu; Ya-Long Guo; Ying-Chun Wang; Fang Huang (Photosynthesis Research, 2022)
Clean and sustainable H 2 production is crucial to a carbon–neutral world. H 2 generation by Chlamydomonas reinhardtii is an attractive approach for solar-H 2 from H 2 O. However, it is currently not large-scalable because of lacking desirable strains with both optimal H 2 productivity and sufficient knowledge of underlying molecular mechanism. We hereby carried out extensive and in-depth investigations of H 2 photoproduction of hpm91 mutant lacking PGR5 (Proton Gradient Regulation 5) toward its up-scaling and fundamental mechanism issues. We show that hpm91 is at least 100-fold scalable (up to 10 L) with continuous H 2 collection of 7287 ml H 2 /10L-HPBR in averagely 26 days under sulfur deprivation. Also, we show that hpm91 is robust and active during sustained H 2 photoproduction, most likely due to decreased intracellular ROS relative to wild type. Moreover, we obtained quantitative proteomic profiles of wild type and hpm91 at four representing time points of H 2 evolution, leading to 2229 and 1350 differentially expressed proteins, respectively. Compared to wild type, major proteome alterations of hpm91 include not only core subunits of photosystems and those related to anti-oxidative responses but also essential proteins in photosynthetic antenna, C/N metabolic balance, and sulfur assimilation toward both cysteine biosynthesis and sulfation of metabolites during sulfur-deprived H 2 production. These results reveal not only new insights of cellular and molecular basis of enhanced H 2 production in hpm91 but also provide additional candidate gene targets and modules for further genetic modifications and/or in artificial photosynthesis mimics toward basic and applied research aiming at advancing solar-H 2 technology.

Characteristic pollutants risk assessment of modified manganese residue utilization in sintered product - Chao-qiang Wang; Ke Liu; De-ming Huang; Qi-cong Huang; Pei-xin Wang; Xu-dong Mei; Shu-chun Li (Environmental Science and Pollution Research, 2022)

Xylomexicanins K-N: limonoids from the leaves and twigs of Xylocarpus granatum - Shao-Jing Li; Li-Kang Zhao; Jin-Jun Chen; Chun-Hua Zhou; Xin-Li Huang; Yi-Bing Wu; Françoise Sauriol; Yu-Cheng Gu; Hiromasa Kiyota (Natural Product Research, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Dietary exposure and risk assessment of phthalic acid esters through a total diet study in Shenzhen, South China - Zhong-Yi Li; Huan Liu; Hui Liu; Wei Huang; Yue Chu; Zhuo-Quan Huang; Chun-Hong Liu (Food Additives & Contaminants: Part A, 2022)

Identification and analysis of B cell epitopes of hemagglutinin of H1N1 influenza virus - Qing Feng; Xiao-Yan Huang; Yang-Meng Feng; Li-jun Sun; Jing-Ying Sun; Yan Li; Xin Xie; Jun Hu; Chun-Yan Guo (Archives of Microbiology, 2022)

Ovary transcriptomic analysis reveals regulation effects of dietary fish oil on hormone, lipid, and glucose metabolism in female adult spotted scat (Scatophagus argus) - Tuo Wang; Zhi-Long Liu; Guang-Li Li; Umar Farouk Mustapha; Charles Brighton Ndandala; Hong-Juan Shi; Chun-Hua Zhu; Hua-Pu Chen; Yang Huang; Dong-Neng Jiang (Frontiers in Marine Science, 2022)
In the aquaculture industry, fish oil is widely used as a nutritional supplement to promote the gonadal maturation of broodstocks, while the mechanism of fish oil on ovary development remain unclear. Herein, female adult spotted scat ( Scatophagus argus ) with most ovaries at phase II were fed with diets containing 8% soybean oil (SO) or 8% fish oil (FO) for 60 days. The final average fish body weight was similar between FO and SO groups. The average gonadosomatic index (GSI) of FO group was higher (non-significant) than that of SO group. Finally, the phase IV ovary of the FO and SO groups were 7 and 5 out of 10, respectively. The serum estradiol (E2) level of the FO group was significantly higher than that of the SO group. The proportions of n-3 long-chain polyunsaturated fatty acids (LC-PUFA, such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)) in the ovaries were much higher in the FO group than in the SO group. These results suggest that the maturity level of the FO group is relatively higher than that of the SO group. Transcriptome sequencing was used to detect the ovary gene expression. Comparatively, the ovary transcriptome analysis showed 68 up-regulated and 193 down-regulated genes in the FO group. The expression levels of Jund and Jun necessary for the ovary maturation were up-regulated in the FO group, while Pparγ and Cxcl12 , which could inhibit the ovary development, were down-regulated in the FO group. Cyp3a27 coding the enzyme for degrading the estrogen was significantly down-regulated in the FO group and coincided with the increase of its serum E2. Kif5b which could regulate the glucose metabolism was up-regulated in the FO group. Serum insulin level was also increased in the FO group. Additionally, Aldh3a2 and Plin2 related to lipid metabolism were significantly down-regulated in the FO group. Briefly, dietary fish oil can influence the expression of genes related to steroid hormone, glucose and lipid metabolism. This study will clarify the mechanism of dietary fish oil in promoting ovary development in teleost fish.

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

New oxindole alkaloids with selective osteoclast inhibitory activity from Gelsemium elegans - Xin Wei; Xiao-Teng Huang; Li-Yan Zhang; Xin-Yue Hu; Wei Zhang; Yong-Qiang Zhou; Hao-Fei Yu; Cai-Feng Ding; Lan-Chun Zhang; Xia Liu; Ying Zhou (Natural Product Research, 2022)

Exploring the effect of COVID-19 on airline environmental efficiency through an interval epsilon-based measure model - Ye Li; Xing-chun Huang; Qiang Cui (Environmental Science and Pollution Research, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Methods for the construction of DEMs of artificial slopes considering morphological features and semantic information - Yan Xu; Ming-wei Zhao; Jie Lu; Chun Wang; Ling Jiang; Can-can Yang; Xiao-li Huang (Journal of Mountain Science, 2022)

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

A new indole alkaloid from the stems of Glycosmis puberula var . craibii - Qi Zhou; Chun-Xiao Jiang; Shou-Yuan Wu; Zi-Ming Chen; Li-Ping Huang (Natural Product Research, 2022)

Micro-Aid Liquid 10 Promotes Growth Performance and Health Status of White Shrimp, Litopenaeus vannamei - Kuo-Chin Huang; Jai-Wei Lee; Ya-Li Shiu; Rolissa Ballantyne; Chun-Hung Liu (Journal of Marine Science and Engineering, 2022)
An experiment was conducted to evaluate the effects of the Micro-Aid Liquid 10 (MAL10) (DPI Global, Porterville, CA, USA), a product made from yucca extract, on growth performance, gut microbiota, and resistance of white shrimp, Litopenaeus vannamei against infectious disease caused by Vibrio alginolyticus. MAL10 was added to shrimp rearing water at different levels of 0 (control), 0.25 mL m3−1 (W0.25), 0.5 mL m3−1 (W0.5), 1 mL m3−1 (W1), and 5 mL m3−1 (W5), respectively, once per week for 70 days. Growth performances, including final body weight, specific growth rate, average daily growth and percentage of weight gain, were significantly improved by adding the MAL10 at levels up to 5 mL m3−1, which may be due to the proliferation of B cells in hepatopancreas of MAL10-treated shrimp. No significant differences in the total viable count and Vibrio-like count in the gut of shrimp were recorded by spread plate method. In the challenge test, shrimp reared in the water supplemented with MAL10 at levels of 1–5 mL m3−1 had significantly lower cumulative mortality after a challenge test with V. alginolyticus compared to shrimp reared in the control, W0.25 and W0.5 groups. Next-generation sequencing indicated that the relative distribution of phylum Proteobacteria in control (80.4%) was higher than the W (77.4%). The proportion of Vibrio was primarily dominant genera in the shrimp intestine and highest in the control group compared to the W group, followed by Spongiimonas, Motilimonas, Demequina, and Shewanella genera. Although there was no statistically significant difference, higher α-diversity indices were recorded in the W5-treated group than in the control group. Therefore, it is considered that MAL10 could be used as a natural alternative in shrimp aquaculture to reduce the risk of infectious disease caused by pathogenic Vibrio and improve the growth performance of white shrimp.

Effect of Temperature on Macroscopic and Microscopic Properties of Sandstone From Qidong Coal Mine - Long-Chuan Deng; Xiao-Zhao Li; Ying-Chao Wang; Yun Wu; Zhen Huang; Chun-lu Jiang (Rock Mechanics and Rock Engineering, 2022)

Adsorption characteristics of cadmium onto aggregates of various acidic red soils from South China - Bin Huang; Dingqiang Li; Zaijian Yuan; Mingguo Zheng; Chen Liang; Yishan Liao; Chun Liu (Journal of Soils and Sediments, 2022)

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Lathyrane diterpenoids from Jatropha podagrica and their antitumor activities in human osteosarcoma cells - Han-Tao Yuan; Qun-Feng Li; Tian Tian; Chun-Yan Zhang; Zou-Qin Huang; Chun-Xiang Fan; Ke Mei; Jie Zhou; Xiao-Xiang Zhai; Si-Bo Li; Jian-Yong Zhu (Natural Product Research, 2021)

Impact of an artificial chute cutoff on the river morphology and flow structure in Sipaikou area of the Upper Yellow River - Qiao Qiao; Chun-guang Li; He-fang Jing; Ling-xiao Huang; Cheng Yang (Journal of Mountain Science, 2021)

Evaluating the Effects Related to Restocking and Stock Replenishment of Penaeus penicillatus in the Xiamen Bay, China - Jia-Qiao Wang; Yi-Jia Shih; Liang-Ming Huang; Jun Li; Wei-Wen Li; Chun-Han Shih; Ta-Jen Chu (Journal of Marine Science and Engineering, 2021)
The quantitative evaluation of restocking and stock replenishment is essential for providing operational feedback and implementing adaptive management for future restoration projects. Since 2010, approximately 700 million juvenile shrimp (Penaeus penicillatus) have been released into Xiamen Bay, Fujian Province, China, each year, through stock replenishment programs. The recruited shrimp were sampled through three-year bottom trawl surveys from 2014 to 2017. The biological characteristics and catch equation were used to evaluate the effect of restocking and stock replenishment. The analysis uses the FAO-ICLARM Stock Assessment Tool (FISAT II) program. In general, there are two sources of recruitments—one from spawning brood stock and the other from released juvenile shrimp. We constructed an evaluation model for an effect evaluation based on Baranov’s catch equation to separate the initial recruitment volume using survey data. The relationship between body weight and total length was W = 1.638 TL2.9307. There is no statistically significant difference between males and females. The von Bertalanffy growth parameters derived for prawns, using FiSAT II, were L∞ = 209.6 mm and K = 0.51 per year. In spring 2014, the initial resource amount was 49,200, while the ratio of effective recruitment and parent amount was 3.92. The survival rate of the released shrimp larvae, 1.88‱, seems to be very unsatisfactory. The resource amount in summer and autumn is higher than in winter and spring. Obviously, the restocking effect is lower and the programs need to be improved. To improve the restocking effect, the replenishment performance should be adjusted to reduce the mortality rate and increase its release effectiveness. Therefore, corresponding implementations are recommended, including standard extensive culture, reduction in stress during transportation, and temporary culture.

NRG1 accelerates the forgetting of fear memories and facilitates the induction of long-term depression in adult mice - Qianqian Cao; Yuan Wei; Jialin Deng; Junfeng Li; Yanhua Huang; Yuke Li; Ji-chun Zhang; Zili Zhang; Song Lin (Psychopharmacology, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

OSL chronology of a Palaeolithic site in a humid subtropical mountainous area of southeast China - Jian-hui Jin; Xiao-yang Wang; Zhen-yu Zhou; Yun-ming Huang; Xue-chun Fan; Xin-xin Zuo; Zhi-zhong Li; Zhi-yong Ling; Yong-qing Ren; Shu-tong Li (Journal of Mountain Science, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Maternal exposure to O3 and NO2 may increase the risk of newborn congenital hypothyroidism: a national data-based analysis in China - Cuifang Qi; Li Shang; Wenfang Yang; Liyan Huang; Liren Yang; Juan Xin; Shanshan Wang; Jie Yue; Lingxia Zeng; Mei Chun Chung (Environmental Science and Pollution Research, 2021)
Maternal exposure to air pollution during pregnancy is associated with adverse outcomes in the offspring, but limited studies focused on the impacts of gaseous air pollution on newborn congenital hypothyroidism (CH). Therefore, a national data-based analysis was conducted to explore the association between maternal exposure to gaseous air pollution and the incidence of CH in China. Annual average exposure levels of SO 2 , NO 2 , CO, and O 3 from January 1, 2014, to December 30, 2014, were acquired from the Chinese Air Quality Online Monitoring and Analysis Platform. The annual incidence of newborn CH from October 1, 2014, to September 30, 2015, was collected from the Chinese Maternal and Child Health Surveillance Network. Temperature and toxic metal in wastewater in 2014 were also collected as covariates. Maternal exposure to O 3 and NO 2 in 1 μg/m 3 level increment was positively associated with newborn CH, with an OR of 1.055 (95% CI 1.011, 1.102) and 1.097 (95% CI 1.019, 1.182) after adjusting for covariates completely. Compared with the lowest level of O 3 , maternal exposure to the 4th quartile of O 3 was positively associated with newborn CH (OR 1.393, 95% CI 1.081, 1.794) after adjusting for covariates completely. And the 3rd and 4th quartiles of NO 2 were associated positively with CH (OR 1.576, 95% CI 1.025, 2.424, and OR 1.553, 95% CI 0.999, 2.414, respectively) compared with the lowest level of NO 2 . By fitting the ROC curve, 93.688 μg/m 3 in O 3 might be used as cutoff to predict the incidence of newborn CH in China.

A Case Study of Whistle Detection and Localization for Humpback Dolphins in Taiwan - Ching-Tang Hung; Wei-Yen Chu; Wei-Lun Li; Yen-Hsiang Huang; Wei-Chun Hu; Chi-Fang Chen (Journal of Marine Science and Engineering, 2021)
In recent years, Taiwan’s government has focused on policies regarding offshore wind farming near the Indo-Pacific humpback dolphin habitat, where marine mammal observation is a critical consideration. The present research developed an algorithm called National Taiwan University Passive Acoustic Monitoring (NTU_PAM) to assist marine mammal observers (MMOs). The algorithm performs whistle detection processing and whistle localization. Whistle detection processing is based on image processing and whistle feature extraction; whistle localization is based on the time difference of arrival (TDOA) method. To test the whistle detection performance, we used the same data to compare NTU_PAM and the widely used software PAMGuard. To test whistle localization, we designed a real field experiment where a sound source projected simulated whistles, which were then recorded by several hydrophone stations. The data were analyzed to locate the moving path of the source. The results show that localization accuracy was higher when the sound source position was in the detection region composed of hydrophone stations. This paper provides a method for MMOs to conveniently observe the migration path and population dynamics of cetaceans without ecological disturbance.

Embryo Development and Behavior in Sea Urchin (Tripneustes gratilla) Under Different Light Emitting Diodes Condition - Yi-Yen Li; Feng-Jie Su; Yi-Jui Hsieh; Tai-Chun Huang; Yung-Song Wang (Frontiers in Marine Science, 2021)
This study aims to evaluate the effect of light-emitting diodes (LEDs) of different wavelengths on the embryonic development, covering behavior, righting behavior, and phototaxis of collector urchins ( Tripneustes gratilla ). The collector urchins were divided into three groups according to the type of LED illumination they received: full-spectrum (400–750 nm wavelength), red light (630 nm), or blue light (450 nm). The results of the embryonic development experiment indicated that the blue LED group had the highest proportion of embryos reaching the prism stage at the 24th hour and the highest proportion of embryos entering the 4-arm pluteus stage, but it also had the highest death rate at the 48th hour. The full-spectrum and red LED groups exhibited similar speeds of embryonic development. In the experiment on covering behavior performed on adult urchins, our findings indicated that the blue LED group gripped the most acrylic sheets for cover, exhibiting the most covering behavior, followed by the full-spectrum group and then the red LED group. Moreover, behavior varied with coloration, as collector urchins with a lower level of melanin exhibited more covering behavior than those with a higher melanin level. In addition, the righting behavior experiments demonstrated that the blue LED group spent the longest time righting themselves. It is possible that the relatively strong stimulation from the blue LED illumination led to a higher level of stress in the collector urchins and hence slowed their righting. The phototaxis experiment revealed the most significant negative phototactic response in collector urchins when they were under the blue LED light, followed by the full-spectrum light; the red LED light did not induce any positive or negative phototactic response in the collector urchins. This experimental result verified collector urchins’ high sensitivity to and dislike of the blue LED light. The study results confirmed that the blue LED light environment accelerated the embryonic development of collector urchins; however, the relatively strong stimulation from that light also caused them to engage in covering behavior or move away from the light. These results indicate that short-wavelength irradiation significantly affects the embryonic development and behavior pattern of this species.

Analysis of unigenes involved in lateral root development in Bupleurum chinense and B. scorzonerifolium - Ma Yu; Hua Chen; Qian Liu; Jing Huang; Kassa Semagn; Dan Liu; Yuchan Li; Bin Yang; Yilian He; Chun Sui; Dabin Hou; Jianhe Wei (Planta, 2021)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Aryl hydrocarbon receptor promotes lipid droplet biogenesis and metabolic shift in respiratory Club cells - Hsueh-Chun Wang; Kwei-Yan Liu; Li-Ting Wang; Shih-Hsien Hsu; Shao-Chun Wang; Shau-Ku Huang (Human Cell, 2021)

Clinical Efficacy of a New Robot-assisted Gait Training System for Acute Stroke Patients - Andy Chien; Fei-Chun Chang; Nai-Hsin Meng; Pei-Yu Yang; Ching Huang; Li-Wei Chou (Journal of Medical and Biological Engineering, 2021)
Purpose Robot-assisted gait rehabilitation has been proposed as a plausible supplementary rehabilitation strategy in stroke rehabilitation in the last decade. However, its exact benefit over traditional rehabilitation remain sparse and unclear. It is therefore the purpose of the current study to comparatively investigate the clinical benefits of the additional robot-assisted training in acute stroke patients compared to standard hospital rehabilitation alone. Methods Ninety acute stroke patients (< 3 month) were recruited. All participants received the standard hospital neurorehabilitation comprises 45–60 min sessions daily for 3 weeks. Sixty patients also received an additional 30 min of robot-assisted gait training with the HIWIN MRG-P100 gait training system after each of the standard neurorehabilitation session. Outcome measures included: 1. Berg Balance Scale (BBS); 2. Brunnstrom Stage; 3. Pittsburgh Sleep Quality Index and 4. Taiwanese Depression Questionnaire (TDQ) which were assessed pre-treatment and then after every five training sessions. Results Both groups demonstrated significant improvement pre- and post-treatment for the BBS (robotic group p = 0.023; control group p = 0.033) but no significant difference (p > 0.1) between the groups were found. However, the robotic training group had more participants demonstrating larger BBS points of improvement as well as greater Brunnstrom stage of improvement, when compared to the control group. No significant within and between group statistical differences (p > 0.3) were found for Pittsburgh Sleep Quality Index and Taiwanese Depression Questionnaire. Conclusion The addition of robotic gait training on top of standard hospital neurorehabilitation for acute stroke patients appear to produce a slightly greater improvement in clinical functional outcomes, which is not transferred to psychological status.

The reproductive regulation of LPXRFa and its receptor in the hypothalamo-pituitary-gonadal axis of the spotted scat (Scatophagus argus) - Yi Zhai; Si-Ping Deng; Jian-Ye Liu; Dong-Neng Jiang; Yang Huang; Chun-Hua Zhu; Guang-Li Li; Ming-Hui Li (Fish Physiology and Biochemistry, 2021)

Impact of air pollution exposure during various periods of pregnancy on term birth weight: a large-sample, retrospective population-based cohort study - Li Shang; Liyan Huang; Liren Yang; Longtao Leng; Cuifang Qi; Guilan Xie; Ruiqi Wang; Leqian Guo; Wenfang Yang; Mei Chun Chung (Environmental Science and Pollution Research, 2021)
Previous studies have suggested that maternal exposure to air pollution might affect term birth weight. However, the conclusions are controversial. Birth data of all term newborns born in Xi’an city of Shaanxi, China, from 2015 to 2018 and whose mother lived in Xi’an during pregnancy were selected form the Birth Registry Database. And the daily air quality data of Xi’an city was collected from Chinese Air Quality Online Monitoring and Analysis Platform. Generalized additive models (GAM) and 2-level binary logistic regression models were used to estimate the effects of air pollution exposure on term birth weight, the risk term low birth weight (TLBW), and macrosomia. Finally, 321521 term newborns were selected, including 4369(1.36%) TLBW infants and 24,960 (7.76%) macrosomia. The average pollution levels of PM 2.5 , PM 10 , and NO 2 in Xi’an city from 2015 to 2018 were higher than national limits. During the whole pregnancy, maternal exposure to PM 2.5 , PM 10 , SO 2 , and CO all significantly reduced the term birth weight and increased the risk of TLBW. However, NO 2 and O 3 exposure have significantly increased the term birth weight, and O 3 even increased the risk of macrosomia significantly. Those effects were also observed in the first and second trimesters of pregnancy. But during the third trimester, high level of air quality index (AQI) and maternal exposure to PM 2.5 , PM 10 , SO 2 , NO 2 , and CO increased the term birth weight and the risk of macrosomia, while O 3 exposure was contrary to this effect. The findings suggested that prenatal exposure to air pollution might cause adverse impacts on term birth weight, and the effects varied with trimesters and pollutants, which provides further pieces of evidence for the adverse effects of air pollution exposure in heavy polluted-area on term birth weight.

Effects of dietary asafoetida (Ferula sinkiangensis K. M. Shen) levels on feeding attraction activity, growth performance, healthiness, and digestive enzyme activity in juvenile Lateolabrax japonicus - Anle Xu; Jingbo Shang-Guan; Zhongbao Li; Zhan Gao; Yong Chun Huang; Qiang Chen (Fish Physiology and Biochemistry, 2020)

Characterization of Ogura CMS fertility-restored interspecific hybrids and backcross progenies from crosses between broccoli and rapeseed - Chun-qing Liu; Guang-qing Li; Xue-qin Yao; Lei Huang; Xin-yan Wu; Zhu-jie Xie (Euphytica, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Deformation and Failure Characteristics of Overburden Under Thin Bedrock and Thick Alluvium: A Case Study in Baodian Coal Mine - Yun Wu; Zhen Huang; Xiao-Zhao Li; Chun-Lu Jiang (Geotechnical and Geological Engineering, 2020)

Short-term effects of meteorological factors, air pollution, and sunspot on childhood hand, foot, and mouth disease in Tianjin, China: a new time series regression, 2014–2018 - Xue-Yue Ji; Li-Yuan Huang; Jia Song; Chun-Nan Fei; Jun Liu; He Liu (Environmental Science and Pollution Research, 2020)

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Gnaq Protects PC12 Cells from Oxidative Damage by Activation of Nrf2 and Inhibition of NF-kB - Xin Sun; Guo-Ping Li; Pu Huang; Lu-Gang Wei; Jia-Zhi Guo; Li-Juan Ao; Di Lu; Shao-Chun Chen (NeuroMolecular Medicine, 2020)

Identification and expression profiling analysis of ascorbate peroxidase gene family in Actinidia chinensis (Hongyang) - Guang-Lian Liao; Qing Liu; Yi-Qi Li; Min Zhong; Chun-Hui Huang; Dong-Feng Jia; Xiao-Biao Xu (Journal of Plant Research, 2020)

Privet golden leaves adapt unexpectedly well to light changes - Ming Yuan; Bo Huang; Li-Hua Dong; Qiao-Hong Han; Yong Yang; Chun-Bang Ding; Chao Hu; Yang-Er Chen; Zhong-Wei Zhang; Shu Yuan (Horticulture, Environment, and Biotechnology, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Effects of prenatal exposure to NO2 on children’s neurodevelopment: a systematic review and meta-analysis - Li Shang; Liren Yang; Wenfang Yang; Liyan Huang; Cuifang Qi; Zixuan Yang; Zhuxuan Fu; Mei Chun Chung (Environmental Science and Pollution Research, 2020)
The neurotoxicity of NO 2 exposure is well-known and potentially causes impaired of neural functions. This review aimed to estimate associations between prenatal NO 2 exposure and neurodevelopment for children. Articles published until May 2019 reported prenatal NO 2 exposure and children’s cognition, psychomotor, language, attention, IQ, and behavior function were searched according to all related terms. The main databases we retrieved included PubMed, Web of Science, Embase, and Cochrane Library. Coefficient was extracted, conversed, and synthesized by random effects meta-analysis. Meanwhile, qualitatively describe would be used for some studies which cannot be synthesized quantitatively for lack of quantity or methods inconsistency. Finally, a total of 3848 citations were searched, and only 10 studies were included. We estimated that per 10 μg/m 3 increase of NO 2 during pregnancy was associated with a − 0.76 point decrease in global psychomotor (95% CI, − 1.34, − 0.18) and a − 0.62 point decrease in fine psychomotor for children (95% CI, − 1.09, − 0.16). But no significant association found in general cognitive and language. In addition, through the literature review, it seemed that prenatal exposure to NO 2 might cause adverse impacts on children’s attention, IQ, and different behaviors, but this requires confirmation from further researches. Our study indicated that prenatal exposure to NO 2 seems to be associated with impaired neural development for children, especially for fine psychomotor. However, further studies are needed for determining the effects of prenatal air pollution exposure on attention, IQ, and behavior.

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

First report of powdery mildew on Bidens pilosa var. radiata and Passiflora edulis f. flavicarpa caused by Golovinomyces circumfusus in Taiwan - Tsung-Chun Lin; Yu-Lun Dai; Cing-Siang You; Jenn-Wen Huang; Chih-Li Wang (Journal of Plant Pathology, 2020)

Abundance and residency dynamics of the Indo‐Pacific humpback dolphin, Sousa chinensis , in the Dafengjiang River Estuary, China - Chongwei Peng; Haiping Wu; Xianyan Wang; Qian Zhu; Thomas A. Jefferson; Chun‐Chieh Wang; Youhou Xu; Jian Li; Hu Huang; Mo Chen; Shiang‐Lin Huang (Marine Mammal Science, 2020)
Robust population size estimates are essential for informing population conservation status. Residency dynamics show population habitat use through time. Population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) has been extensively investigated in Chinese waters, but their residency dynamics are rarely known. Mark‐recapture analysis based on photo‐identification records was applied to humpback dolphins in the Dafengjiang River Estuary habitat, one of the key habitats in the northern Beibu Gulf, China. Movement analyses based on lagged identification rate indicated the humpback dolphins spent, on average, 78.5 days inside and 46.9 days outside the survey area. Within the study area, the humpback dolphin abundance was 83 identifiable dolphins. A total of 353–430 humpback dolphins, estimated by POPAN modeling, were involved in this fluid habitat‐use dynamic. Robust Design analysis showed strong seasonality in humpback dolphin abundance and emigration probability, implying a movement‐ and habitat‐use pattern likely associated with spatiotemporal distribution of oceanographic characteristics and prey occurrences. Population surveys and conservation measures currently conducted in Chinese waters seldom consider seasonality in movements between habitat patches, which can be addressed by genetic analyses across habitats and cross‐matching photo‐identification records among neighboring habitats.

Chloroplast genome of an extremely endangered conifer Thuja sutchuenensis Franch.: gene organization, comparative and phylogenetic analysis - Tao Yu; Bing-Hong Huang; Yuyang Zhang; Pei-Chun Liao; Jun-Qing Li (Physiology and Molecular Biology of Plants, 2020)

Sparse constrained encoding multi-source full waveform inversion method based on K-SVD dictionary learning - Yun-dong Guo; Jian-Ping Huang; Cui Chao; Zhen-Chun Li; Qing-Yang Li; Wei Wei (Applied Geophysics, 2020)

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

Contribution of skeletal muscular glycine to rapid antidepressant effects of ketamine in an inflammation-induced mouse model of depression - Niannian Huang; Yue Wang; Gaofeng Zhan; Fan Yu; Shan Li; Dongyu Hua; Riyue Jiang; Shiyong Li; Yeshun Wu; Ling Yang; Bin Zhu; Fei Hua; et al. (Psychopharmacology, 2019)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Autotrophic Bacterial Community and Microbial CO2 Fixation Respond to Vegetation Restoration of Eroded Agricultural Land - Haibing Xiao; Zhongwu Li; Chuxiong Deng; Lin Liu; Jia Chen; Bin Huang; Xiaodong Nie; Chun Liu; Danyang Wang; Jieyu Jiang (Ecosystems, 2019)

Multiparameter least-squares reverse time migration for acoustic—elastic coupling media based on ocean bottom cable data - Ying-Ming Qu; Chong-Peng Huang; Chang Liu; Chang Zhou; Zhen-Chun Li; Qurmet Worral (Applied Geophysics, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Synthesis of oleanolic acid/ursolic acid/glycyrrhetinic acid-hydrogen sulfide donor hybrids and their antitumor activity - Li-xin Sheng; Jia-yan Huang; Chun-mei Liu; Ju-zheng Zhang; Ke-guang Cheng (Medicinal Chemistry Research, 2019)

Genesis of the Binh Do Pb-Zn Deposit in Northern Vietnam: Evidence from H-O-S-Pb Isotope Geochemistry - Chaowen Huang; Huan Li; Chun-Kit Lai (Journal of Earth Science, 2019)

Biodiversity and antifouling activity of fungi associated with two soft corals from the South China Sea - Xiao-Yong Zhang; Hui-Li Hao; Stanley Chun Kwan Lau; Huai-You Wang; Yu Han; Li-Mei Dong; Ri-Ming Huang (Archives of Microbiology, 2019)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Impact of lower and higher alcohol additions to diesel on the combustion and emissions of a direct-injection diesel engine - Xinling Li; Chun Guan; Ke Yang; Chun Shun Cheung; Zhen Huang (Environmental Science and Pollution Research, 2019)

Integrated rockfall hazard and risk assessment along highways: An example for Jiuzhaigou area after the 2017 Ms 7.0 Jiuzhaigou earthquake, China - Xiao-ning Li; Si-xiang Ling; Chun-wei Sun; Jian-xiang Xu; Tao Huang (Journal of Mountain Science, 2019)

Correction to: Low-Grade Inflammation Aggravates Rotenone Neurotoxicity and Disrupts Circadian Clock Gene Expression in Rats - Huan Li; Sheng Song; Yuan Wang; Chun Huang; Feng Zhang; Jie Liu; Jau-Shyong Hong (Neurotoxicity Research, 2019)

Giant landslide displacement analysis using a point cloud set conflict technique: a case in Xishancun landslide, Sichuan, China - Chun Liu; Xiaohang Shao; Hangbin Wu; Nan Li; Tengteng Qu; Giulia Dotta; Yu Huang (International Journal of Remote Sensing, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Low-Grade Inflammation Aggravates Rotenone Neurotoxicity and Disrupts Circadian Clock Gene Expression in Rats - Huan Li; Sheng Song; Yuan Wang; Chun Huang; Feng Zhang; Jie Liu; Jau-Shyong Hong (Neurotoxicity Research, 2019)

Ore-Forming Fluids Characteristics and Metallogenesis of the Anjing Hitam Pb-Zn Deposit in Northern Sumatra, Indonesia - Chaowen Huang; Gaofeng Du; Huajun Jiang; Jianfeng Xie; Daohan Zha; Huan Li; Chun-Kit Lai (Journal of Earth Science, 2019)

Effect of biodiesel on PAH, OPAH, and NPAH emissions from a direct injection diesel engine - Xinling Li; Ye Zheng; Chun Guan; Chun Shun Cheung; Zhen Huang (Environmental Science and Pollution Research, 2018)

PGC-1α–FNDC5–BDNF signaling pathway in skeletal muscle confers resilience to stress in mice subjected to chronic social defeat - Gaofeng Zhan; Niannian Huang; Shan Li; Dongyu Hua; Jie Zhang; Xi Fang; Ning Yang; Ailin Luo; Chun Yang (Psychopharmacology, 2018)

Source tectonic dynamics features of Jiuzhaigou Ms 7.0 earthquake in Sichuan Province, China - Shu-jian Yi; Chun-hao Wu; Yu-sheng Li; Chao Huang (Journal of Mountain Science, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

The vanadium isotopic composition of L ordinary chondrites - Yongli Xue; Chun-hui Li; Yuhan Qi; Chuantong Zhang; Bingkui Miao; Fang Huang (Acta Geochimica, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Seismogenic fault and topography control on the spatial patterns of landslides triggered by the 2017 Jiuzhaigou earthquake - Chun-hao Wu; Peng Cui; Yu-sheng Li; Irasema Alcántara Ayala; Chao Huang; Shu-jian Yi (Journal of Mountain Science, 2018)

Optimization of the culture medium for recombinant protein production under the control of the αAmy3 promoter in a rice suspension-cultured cell expression system - Yu-Kuo Liu; Chia-Wei Lu; Jer-Yuan Chang; Ching-Fan Lu; Chia-Chun Tan; Li-Fen Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

Characteristics and failure mechanism of an ancient earthquake-induced landslide with an extremely wide distribution area - Chao Huang; Yu-sheng Li; Shu-jian Yi; Kai Liu; Chun-hao Wu (Journal of Mountain Science, 2018)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Reflection full-waveform inversion using a modified phase misfit function - Chao Cui; Jian-Ping Huang; Zhen-Chun Li; Wen-Yuan Liao; Zhe Guan (Applied Geophysics, 2017)

Three-dimensional arbitrarily anisotropic modeling for time-domain airborne electromagnetic surveys - Wei Huang; Fang Ben; Chang-Chun Yin; Qing-Min Meng; Wen-Jie Li; Gui-Xiang Liao; Shan Wu; Yong-Zai Xi (Applied Geophysics, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Improving the resolution of seismic traces based on the secondary time–frequency spectrum - De-Ying Wang; Jian-Ping Huang; Xue Kong; Zhen-Chun Li; Jiao Wang (Applied Geophysics, 2017)

Evaluation of the antioxidant property and effects in Caenorhabditis elegans of Xiangxi flavor vinegar, a Hunan local traditional vinegar - Run-ting Huang; Qing Huang; Gen-liang Wu; Chun-guang Chen; Zong-jun Li (Journal of Zhejiang University-SCIENCE B, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

The cohesion stabilizer sororin favors DNA repair and chromosome segregation during mouse oocyte meiosis - Chun-Jie Huang; Yi-Feng Yuan; Di Wu; Faheem Ahmed Khan; Xiao-Fei Jiao; Li-Jun Huo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Preconditioned prestack plane-wave least squares reverse time migration with singular spectrum constraint - Chuang Li; Jian-Ping Huang; Zhen-Chun Li; Rong-Rong Wang (Applied Geophysics, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

Compost as a Soil Amendment to Remediate Heavy Metal-Contaminated Agricultural Soil: Mechanisms, Efficacy, Problems, and Strategies - Mei Huang; Yi Zhu; Zhongwu Li; Bin Huang; Ninglin Luo; Chun Liu; Guangming Zeng (Water, Air, & Soil Pollution, 2016)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Preliminary studies on the dynamic prediction method of rainfall-triggered landslide - Yue-li Chen; De-hui Chen; Ze-chun Li; Jun-bao Huang (Journal of Mountain Science, 2016)

Evaluating the Relative Importance of Groundwater Recharge Sources in a Subtropical Alluvial Plain Using Tracer-Based Ternary End Member Mixing Analysis (EMMA) - Tsung-Ren Peng; Chun-Chun Huang; Jui-Er Chen; Wen-Jun Zhan; Li-Wei Chiang; Liang-Cheng Chang (Water Resources Management, 2016)

Prismatic and full-waveform joint inversion - Ying-Ming Qu; Zhen-Chun Li; Jian-Ping Huang; Jin-Li Li (Applied Geophysics, 2016)

Nitrogen-Fixing and Plant Growth-Promoting Ability of Two Endophytic Bacterial Strains Isolated from Sugarcane Stalks - Yong-Xiu Xing; Chun-Yan Wei; Yao Mo; Li-Tao Yang; Si-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Overexpression of PGC-1α Influences Mitochondrial Signal Transduction of Dopaminergic Neurons - Qinyong Ye; Wanling Huang; Dongzhu Li; Erwang Si; Juhua Wang; Yingqing Wang; Chun Chen; Xiaochun Chen (Molecular Neurobiology, 2016)

Factorial Analysis of Variables Influencing Mechanical Characteristics in Le Fort I Osteotomy Using FEA and Statistics-Based Taguchi Method - Shao-Fu Huang; Lun-Jou Lo; Chun-Li Lin (Journal of Medical and Biological Engineering, 2016)

Inhibitory effect of baicalin on allergic response in ovalbumin-induced allergic rhinitis guinea pigs and lipopolysaccharide-stimulated human mast cells - Yun-jiang Zhou; Hu Wang; He-huan Sui; Li Li; Chun-ling Zhou; Jia-jun Huang (Inflammation Research, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Agriculture driving male expansion in Neolithic Time - Chuan-Chao Wang; Yunzhi Huang; Xue’er Yu; Chun Chen; Li Jin; Hui Li (Science China Life Sciences, 2016)

The proteome and phosphoproteome of maize pollen uncovers fertility candidate proteins - Qing Chao; Zhi-fang Gao; Yue-feng Wang; Zhe Li; Xia-he Huang; Ying-chun Wang; Ying-chang Mei; Biligen-gaowa Zhao; Liang Li; Yu-bo Jiang; Bai-chen Wang (Plant Molecular Biology, 2016)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Microbial communities of an arable soil treated for 8 years with organic and inorganic fertilizers - Chen Chen; Jianan Zhang; Min Lu; Chun Qin; Yahua Chen; Li Yang; Qiwei Huang; Jichen Wang; Zhenguo Shen; Qirong Shen (Biology and Fertility of Soils, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Increased expression of long noncoding RNAs LOC100652951 and LOC100506036 in T cells from patients with rheumatoid arthritis facilitates the inflammatory responses - Ming-Chi Lu; Hui-Chun Yu; Chia-Li Yu; Hsien-Bin Huang; Malcolm Koo; Chien-Hsueh Tung; Ning-Sheng Lai (Immunologic Research, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

Olfactory Deprivation Hastens Alzheimer-Like Pathologies in a Human Tau-Overexpressed Mouse Model via Activation of cdk5 - Ke Li; Fang-Fang Liu; Chun-Xue He; He-Zhou Huang; Ao-Ji Xie; Fan Hu; Dan Liu; Jian-Zhi Wang; Ling-Qiang Zhu (Molecular Neurobiology, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

Therapeutic Retrobulbar Inhibition of STAT3 Protects Ischemic Retina Ganglion Cells - Mansin Wong; Ying Li; Shang Li; Shaodan Zhang; Weiyi Li; Pei Zhang; Chaoran Chen; Colin J. Barnstable; Samuel S. Zhang; Chun Zhang; Ping Huang (Molecular Neurobiology, 2015)

Fluorofenidone protects against renal fibrosis by inhibiting STAT3 tyrosine phosphorylation - Juan Tang; Chun-yan Liu; Miao-miao Lu; Jing Zhang; Wen-juan Mei; Wen-jun Yang; Yan-yun Xie; Ling Huang; Zhang-zhe Peng; Qiong-jing Yuan; Ji-shi Liu; Gao-yun Hu; et al. (Molecular and Cellular Biochemistry, 2015)

Effects of cold acclimation on sugar metabolism and sugar-related gene expression in tea plant during the winter season - Chuan Yue; Hong-Li Cao; Lu Wang; Yan-Hua Zhou; Yu-Ting Huang; Xin-Yuan Hao; Yu-Chun Wang; Bo Wang; Ya-Jun Yang; Xin-Chao Wang (Plant Molecular Biology, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

Marasmius albopurpureus, a new species of section Globulares from Baili Island, China - Chao-Qun Wang; Tai-Hui Li; Hao Huang; Ye-Wei Xia; Chun-Ying Deng; Wang-Qiu Deng (Mycological Progress, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

CDK5 Contributes to Neuronal Apoptosis via Promoting MEF2D Phosphorylation in Rat Model of Intracerebral Hemorrhage - Kaifu Ke; Jiabing Shen; Yan Song; Maohong Cao; Hongjian Lu; Chun Liu; Jianhong Shen; Aihong Li; Jie Huang; Haidan Ni; Xiaomei Chen; Yonghua Liu (Journal of Molecular Neuroscience, 2015)

Impact of LPS-Induced Cardiomyoblast Cell Apoptosis Inhibited by Earthworm Extracts - Ping-Chun Li; Yun-Chen Tien; Cecilia Hsuan Day; Peiying Pai; Wei-Wen Kuo; Tung-Sheng Chen; Chia-Hua Kuo; Chang-Hai Tsai; Da-Tong Ju; Chih-Yang Huang (Cardiovascular Toxicology, 2015)

Do organophosphate-based traps reduce control efficiency of resistant tephritid flies? - Ju-Chun Hsu; Li-Hsin Huang; Hai-Tung Feng; Wen-Yin Su (Journal of Pest Science, 2015)

Epidemical features of HAdV-3 and HAdV-7 in pediatric pneumonia in Chongqing, China - Ying Wo; Qing-Bin Lu; Dou-Dou Huang; Xiao-Kun Li; Chen-Tao Guo; Hong-Yu Wang; Xiao-Ai Zhang; Wei Liu; Wu-Chun Cao (Archives of Virology, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Sedimentary and hydrological studies of the Holocene palaeofloods in the Shanxi-Shaanxi Gorge of the middle Yellow River, China - Xiaogang Li; Chun Chang Huang; Jiangli Pang; Xiaochun Zha; Yugai Ma (International Journal of Earth Sciences, 2015)

A Brassica napus PHT1 phosphate transporter, BnPht1;4, promotes phosphate uptake and affects roots architecture of transgenic Arabidopsis - Feng Ren; Cai-Zhi Zhao; Chun-Sen Liu; Ke-Lin Huang; Qian-Qian Guo; Li-Li Chang; Huan Xiong; Xue-Bao Li (Plant Molecular Biology, 2014)

Pai-1 Gene Variants and COC Use Are Associated with Stroke Risk: A Case-Control Study in the Han Chinese Women - Xiaoping Huang; Ying Li; Zhizheng Huang; Chun Wang; Zhenlin Xu (Journal of Molecular Neuroscience, 2014)

Isolation and characterization of twenty-five polymorphic microsatellite markers in Siniperca scherzeri Steindachner and cross-species amplification - WEI HUANG; XU-FANG LIANG; CHUN-MEI QU; JI LI; LIANG CAO (Journal of Genetics, 2014)

A new lignan from the roots of Syringa pinnatifolia - Li-Wei Shao; Chun-Hua Wang; Guo-Qiang Li; Xiao-Jun Huang; Zheng Li; Guo-Cai Wang (Natural Product Research, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Characterization of Arabidopsis Tubby-like proteins and redundant function of AtTLP3 and AtTLP9 in plant response to ABA and osmotic stress - Yan Bao; Wei-Meng Song; Yan-Li Jin; Chun-Mei Jiang; Yang Yang; Bei Li; Wei-Jie Huang; Hua Liu; Hong-Xia Zhang (Plant Molecular Biology, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

The differentiation and development of pistils of hermaphrodites and pistillodes of males in androdioecious Osmanthus fragrans L. and implications for the evolution to androdioecy - Yi-Chun Xu; Li-Hua Zhou; Shao-Qing Hu; Ri-Ming Hao; Chong-jing Huang; Hong-Bo Zhao (Plant Systematics and Evolution, 2014)

BIG1, a Brefeldin A-Inhibited Guanine Nucleotide-Exchange Factor, Is Required for GABA-Gated Cl– Influx Through Regulation of GABAA Receptor Trafficking - Cuixian Li; Shaorui Chen; Yang Yu; Chun Zhou; Ying Wang; Kang Le; Dong Li; Weiwei Shao; Liang Lu; Yan You; Jin Peng; Heqing Huang; et al. (Molecular Neurobiology, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Growth differentiation factor 9 of Megalobrama amblycephala: molecular characterization and expression analysis during the development of early embryos and growing ovaries - Chun Xiao Huang; Xin Lan Wei; Nan Chen; Jie Zhang; Li Ping Chen; Wei Min Wang; Jun Yan Li; Huan Ling Wang (Fish Physiology and Biochemistry, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Synthesis, Fluorescence Properties and Theoretical Calculations of Novel Stilbene Derivatives Based on 1,3,4-Oxadiazole Bearing Anthracene Core - Xinwei Li; Huixiong Lu; Daohang He; Chun Luo; Jianjun Huang (Journal of Fluorescence, 2013)

Population genetic structure, local adaptation, and conservation genetics of Kandelia obovata - Yu Ruan; Bing-Hong Huang; Shih-Jie Lai; Yu-Ting Wan; Jun-Qing Li; Shong Huang; Pei-Chun Liao (Tree Genetics & Genomes, 2013)

Revealing storage-area relationship of open water in ungauged subalpine wetland — Napahai in Northwest Yunnan, China - Jie Li; Jin-ming Hu; Wei Deng; Sheng-li Huang; Hai-feng Jia; Chun-ling Zhu; Huai-xiu Luo (Journal of Mountain Science, 2013)
Mountains and plateaus in Southwest China contain many subalpine and alpine wetlands, with significant hydroecological functions. But ungauged or poorly gauged conditions limit the study and understanding of hydrological regimes of these wetland types. This study selects an ungauged subalpine wetland — Napahai in Northwest Yunnan, China — as a case for developing a practical approach to revealing its storage-area relationship of open water. A Trimble R8 GNSS (Global Navigation Satellites Systems) RTK (Real-time Kinematic system) and sonar fathometer were used to survey fine-resolution elevation data and generate a digital elevation model of the Napahai Wetland. Forty-four Landsat images from 1987 to 2011 were collected, and the Normalized Difference Water Index was used to classify open water features in the area. The area of open water in Napahai was calculated for each phase. With these data and a developed conceptual model, the storage of open water for each phase was estimated using ArcGIS tools. Both storage and area of open water showed significant intra-annual and inter-annual variations. In the rainy season, the monthly change of average storage of open water in Napahai showed about 1–2 months lag behind mean monthly rainfall. The storage-area relationship of open water was well fit by a power function equation ( R 2 ≈0.91, n =44). This study indicates that if detailed elevations are available for similarly ungauged subalpine wetlands in Southwest China, researchers can use this practical approach to estimate multi-temporal areas and storages and reveal the storage-area relationship of open water in the wetlands. The study provided valuable information of this case wetland for optimizing its hydro-ecological managements and a new method to wetland researchers and managers for the hydrological study of similarly ungauged wetland complex.

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

Regional and cell-type specific distribution of HDAC2 in the adult mouse brain - Zhi-Gang Yao; Ling Zhang; Lan Huang; Hua Zhu; Ying Liu; Chun-Mei Ma; Shu-Li Sheng; Chuan Qin (Brain Structure and Function, 2013)

Protection by chrysin, apigenin, and luteolin against oxidative stress is mediated by the Nrf2-dependent up-regulation of heme oxygenase 1 and glutamate cysteine ligase in rat primary hepatocytes - Chin-Shiu Huang; Chong-Kuei Lii; Ai-Hsuan Lin; Yu-Wen Yeh; Hsien-Tsung Yao; Chien-Chun Li; Tsu-Shing Wang; Haw-Wen Chen (Archives of Toxicology, 2013)

A Highly Sensitive Fluorescent Probe for HClO and Its Application in Live Cell Imaging - Qing-Ping Zuo; Zuo-Jun Li; Yong-Hua Hu; Bin Li; Li-Hua Huang; Chun-Jiang Wang; Shi-Kun Liu; Hai-Qiang Liao (Journal of Fluorescence, 2012)

Increased risk of stroke in oral contraceptive users carried replicated genetic variants: a population-based case–control study in China - Chun Wang; Ying Li; Huiqiao Li; Tao Sun; Guangfu Jin; Zhiming Sun; Jian Zhou; Lei Ba; Zhizheng Huang; Jianling Bai (Human Genetics, 2012)

Ds transposon is biased towards providing splice donor sites for exonization in transgenic tobacco - Kuo-Chan Huang; Hsiu-Chun Yang; Kuan-Te Li; Li-yu Daisy Liu; Yuh-Chyang Charng (Plant Molecular Biology, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Quantitative assessment of the effect of MTHFR polymorphisms on the risk of lung carcinoma - Yao Zhang; Guo Qiang Chen; Yong Ji; Bin Huang; Wei Sheng Shen; Li Chun Deng; Lei Xi; Xiang Ming Cao (Molecular Biology Reports, 2012)

Relative bioavailability and pharmacokinetic comparison of two different enteric formulations of omeprazole - Jian Liu; Jian-zhong Shentu; Li-hua Wu; Jing Dou; Qi-yang Xu; Hui-li Zhou; Guo-lan Wu; Ming-zhu Huang; Xing-jiang Hu; Jun-chun Chen (Journal of Zhejiang University-SCIENCE B, 2012)

An essential role for the Id1/PI3K/Akt/NFkB/survivin signalling pathway in promoting the proliferation of endothelial progenitor cells in vitro - Wei Li; Hang Wang; Chun-yan Kuang; Jin-kun Zhu; Yang Yu; Zhe-xue Qin; Jie Liu; Lan Huang (Molecular and Cellular Biochemistry, 2012)

Scattering spectrum properties and their relationship to biogeochemical parameters: a case study in Taihu Lake - Chang-Chun Huang; Yun-Mei Li; Qiao Wang; De-Yong Sun; Cheng-Feng Le; Kun Shi (Limnology, 2012)

Chemical and pharmacological studies of Oplopanax horridus, a North American botanical - Tyler Calway; Guang-Jian Du; Chong-Zhi Wang; Wei-Hua Huang; Jing Zhao; Shao-Ping Li; Chun-Su Yuan (Journal of Natural Medicines, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Characterization of acute renal allograft rejection by proteomic analysis of renal tissue in rat - Gang Chen; Jing-bin Huang; Jie Mi; Yun-feng He; Xiao-hou Wu; Chun-li Luo; Si-min Liang; Jia-bing Li; Ya-xiong Tang; Jie Li (Molecular Biology Reports, 2012)

Survey of antioxidant capacity and phenolic composition of blueberry, blackberry, and strawberry in Nanjing - Wu-yang Huang; Hong-cheng Zhang; Wen-xu Liu; Chun-yang Li (Journal of Zhejiang University-SCIENCE B, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Association study of single nucleotide polymorphisms in pre-miRNA and rheumatoid arthritis in a Han Chinese population - Bin Yang; Jun Long Zhang; Yun Ying Shi; Dong Dong Li; Jie Chen; Zhuo Chun Huang; Bei Cai; Xing Bo Song; Li Xin Li; Bin Wu Ying; Lan Lan Wang (Molecular Biology Reports, 2011)

Activation of regulatory T cells instigates functional down-regulation of cytotoxic T lymphocytes in human breast cancer - Chao-Hsu Li; Wen-Hong Kuo; Wen-Chun Chang; Su-Cheng Huang; King-Jen Chang; Bor-Ching Sheu (Immunologic Research, 2011)

A DNA vaccine expressing CFP21 and MPT64 fusion protein enhances BCG-induced protective immunity against Mycobacterium tuberculosis infection in mice - Chun Wang; Zhenhua Chen; Ruiling Fu; Ying Zhang; Lingxia Chen; Li Huang; Jinjin Li; Chunwei Shi; Xionglin Fan (Medical Microbiology and Immunology, 2011)

A neural-network model to retrieve CDOM absorption from in situ measured hyperspectral data in an optically complex lake: Lake Taihu case study - De Yong Sun; Yun Mei Li; Qiao Wang; Heng Lu; Cheng Feng Le; Chang Chun Huang; Shao Qi Gong (International Journal of Remote Sensing, 2011)

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Effect of dehydroepiandrosterone on aggrecanase expression in articular cartilage in a rabbit model of osteoarthritis - Kai Huang; Chun Zhang; Xiao-wen Zhang; Jia-peng Bao; Li-dong Wu (Molecular Biology Reports, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Overcoming pre-fertilization barriers in the wide cross between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. nankingense (Nakai) Tzvel. by using special pollination techniques - Chun-Qing Sun; Zhi-Zhe Huang; Yan-Li Wang; Fa-Di Chen; Nian-Jun Teng; Wei-Min Fang; Zhao-Lei Liu (Euphytica, 2011)

A fibrillar form of fibronectin induces apoptosis by activating SHP-2 and stress fiber formation - Chun-Yung Huang; Chi-Ming Liang; Chiao-Li Chu; Jei-Ming Peng; Shu-Mei Liang (Apoptosis, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Acacetin, a flavonoid, inhibits the invasion and migration of human prostate cancer DU145 cells via inactivation of the p38 MAPK signaling pathway - Kun-Hung Shen; Shun-Hsing Hung; Li-Te Yin; Chun-Shui Huang; Chang-Hung Chao; Chein-Liang Liu; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2010)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Development of twelve polymorphic microsatellite loci in polyploid endangered Omphalogramma vincaeflora Franch. (Primulaceae) - Yuan Huang; Yong Li; Xiao Hu; Xue-Jun Ge; Chang-Qin Zhang; Chun-Lin Long (Conservation Genetics, 2009)

Allocating the costs of multi-purpose water resource development: a case study of Chi-Chi Weir in Taiwan - Li-Chun Huang; Ching-Kai Hsiao; Sheng-Feng Kuo (Paddy and Water Environment, 2009)

Association of the mutation for the human carboxypeptidase E gene exon 4 with the severity of coronary artery atherosclerosis - En-Zhi Jia; Jie Wang; Zhi-Jian Yang; Tie-Bing Zhu; Lian-Sheng Wang; Hui Wang; Chun-Jian Li; BO Chen; Ke-Jiang Cao; Jun Huang; Wen-Zhu Ma (Molecular Biology Reports, 2009)

DETA/NONOate, a nitric oxide donor, produces antidepressant effects by promoting hippocampal neurogenesis - Yao Hua; Xin-Yan Huang; Li Zhou; Qi-Gang Zhou; Yao Hu; Chun-Xia Luo; Fei Li; Dong-Ya Zhu (Psychopharmacology, 2008)

Determination of risperidone in human plasma by HPLC-MS/MS and its application to a pharmacokinetic study in Chinese volunteers - Ming-zhu Huang; Jian-zhong Shentu; Jun-chun Chen; Jian Liu; Hui-li Zhou (Journal of Zhejiang University-SCIENCE B, 2008)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Genetic diversity and relationships among safflower (Carthamus tinctorius L.) analyzed by inter-simple sequence repeats (ISSRs) - Yu-Xia Yang; Wei Wu; You-Liang Zheng; Li Chen; Ren-Jian Liu; Chun-Yan Huang (Genetic Resources and Crop Evolution, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Independent [Ca2+]i increases and cell proliferation induced by the carcinogen safrole in human oral cancer cells - Jong-Khing Huang; Chun-Jen Huang; Wei-Chuan Chen; Shiuh-Inn Liu; Shu-Shong Hsu; Hong-Tai Chang; Li-Ling Tseng; Chiang-Ting Chou; Chih-Hung Chang; Chung-Ren Jan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Climatic Aridity and the Relocations of the Zhou Culture in the Southern Loess Plateau of China - Chun Chang Huang; Shichao Zhao; Jiangli Pang; Qunying Zhou; Shue Chen; Pinghua Li; Longjiang Mao; Min Ding (Climatic Change, 2003)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Developing an improved In vitro propagation system for slow-growing species using garcinia mangostana L. (mangosteen) - Li-Chun Huang; Bau-Liang Huang; Chiu Hui Wang; Ching-I Kuo; Toshio Murashige (In Vitro Cellular & Developmental Biology - Plant, 2000)

In vitro evaluation of GL331's cancer cell killing and apoptosis-inducing activity in combination with other chemotherapeutic agents - Tze-Sing Huang; Chih-Hung Shu; Chun-Chung Lee; Li-Tzong Chen; Jacqueline Whang-Peng (Apoptosis, 2000)

A Novel Podophyllotoxin-Derived Compound GL331 Is More Potent than Its Congener VP-16 in Killing Refractory Cancer Cells - Tze-Sing Huang; Chun-Chung Lee; Yee Chao; Chih-Hung Shu; Li-Tzong Chen; Li-Li Chen; Min-Hsiung Chen; Chiou-Chung Yuan; Jacqueline Whang-Peng (Pharmaceutical Research, 1999)

A micropropagation protocol forCinnamomum camphora - Li-Chun Huang; Bau-Liang Huang; Toshio Murashige (In Vitro Cellular & Developmental Biology - Plant, 1998)